Polyethylene composition and biaxially stretched film comprising same
By developing a polyethylene composition containing ethylene-α olefin copolymer and optimizing the backbone weight average molecular weight of its high crystalline fraction, the problem of the lack of tensile stability in the biaxial stretching process of existing polyethylene resins is solved, and a biaxial stretched film with high shrinkage resistance, printing suitability and transparency is achieved.
Patent Information
- Application Number
- CN202380064744.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-21
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-18
AI Technical Summary
The existing polyethylene resin lacks tensile stability during biaxial stretching, resulting in cracking and melting, making it difficult to apply to biaxial stretching films.
A polyethylene composition is developed, including an ethylene-α olefin copolymer, and the backbone weight average molecular weight of the high crystalline fraction is optimized by cross-fractionation chromatography to adjust the balance between mechanical properties and elongation.
A biaxially stretched film with high shrinkage resistance, printing suitability and transparency while maintaining excellent mechanical properties, productivity and tensile stability.
Smart Images

Figure BDA0005302277190000051 
Figure BDA0005302277190000101 
Figure BDA0005302277190000103
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0120055 filed on September 22, 2022, and No. 10-2023-0126269 filed on September 21, 2023, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety. Technical Field
[0003] The present invention relates to a polyethylene composition suitable for a biaxially stretched film by having high shrinkage resistance, printability and transparency while maintaining excellent mechanical properties. Background Art
[0004] Film products made of linear low-density polyethylene (LLDPE) and / or high-density polyethylene (HDPE) are widely used in packaging (such as commodity bags, shopping bags, food and special product packaging) and industrial liners. In these applications, shrink films that can wrap the goods while maintaining their shape are mainly used to prevent the products from being touched during display.
[0005] In particular, among these shrink films, biaxially stretched polymer films have excellent mechanical properties, productivity, and printability, and are therefore widely used for packaging. Commercially available packaging films generally use BOPP (biaxially oriented polypropylene), BOPET (biaxially oriented polyethylene terephthalate), or BOPA (biaxially oriented polyamide) for the printing layer, and LLDPE for the sealing layer. These composite materials cannot be recycled, and due to regulations on the reuse of packaging materials, the demand for single materials is increasing. Therefore, research and development is being conducted to manufacture a single-material packaging film by replacing the film of the printing layer with a biaxially oriented polyethylene (BOPE) film.
[0006] However, commercially available polyethylene (PE) resins do not have sufficient tensile stability, and phenomena such as cracking and melting may occur during the stretching process, making it difficult to apply them to biaxial stretching processes. In order to ensure tensile stability, products in the form of polyethylene compositions containing resins with low density and high melt index have been developed. However, due to low stiffness, shrinkage and impact resistance, the compositions described above are not suitable as PE resins for biaxially stretched films.
[0007] Therefore, there is a need for a method of selecting a PE resin having a molecular structure favorable for stretching and selecting an appropriate composition, thereby providing a PE composition for biaxial stretching that exhibits stretching stability during biaxial stretching and has good film mechanical properties. Summary of the invention
[0008] Technical issues
[0009] The present invention relates to a polyethylene composition capable of preparing a biaxially stretched film having high shrinkage resistance, printability and transparency while maintaining excellent mechanical properties, productivity and stretching stability, and also relates to a biaxially stretched film comprising the polyethylene composition.
[0010] Technical Solution
[0011] According to one embodiment of the present invention, there is provided a polyethylene composition comprising at least one ethylene-alpha olefin copolymer, wherein the main chain weight average molecular weight (Mw) of a high crystalline fraction eluted above 90° C. from a cross fractionation chromatography (CFC) analysis of the polyethylene composition is main,T≥90℃ ) is less than 150000 g / mol.
[0012] In another embodiment of the present invention, a biaxially stretched film is provided, comprising the polyethylene composition of the above embodiment.
[0013] Hereinafter, a polyethylene composition and a biaxially oriented film according to embodiments of the present invention will be described in detail.
[0014] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0015] Singular forms are intended to include plural forms as well, unless the context clearly indicates otherwise.
[0016] In the present invention, the terms “comprises”, “includes” or “has” are used to describe the stated features, quantities, steps, components or a combination thereof, and do not exclude the addition of one or more other features, quantities, steps, components or a combination thereof.
[0017] The term “about” or “substantially” is intended to have a meaning approximate to a numerical value or range specified with an allowable error, and is intended to prevent the exact or absolute numerical values disclosed for understanding the present invention from being illegally or unfairly used by any unreasonable third party.
[0018] Furthermore, in the present invention, the (co)polymer is intended to include both homopolymers and copolymers.
[0019] Unless otherwise defined herein, "copolymerization" may mean block copolymerization, random copolymerization, graft copolymerization or alternating copolymerization, and "copolymer" means block copolymer, random copolymer, graft copolymer or alternating copolymer.
[0020] Since the present invention can be modified in various ways and has various forms, its specific implementation is shown by way of example and will be described in detail. However, it is not intended to limit the present invention to the specific form disclosed, and it should be understood that the present invention includes all modifications, equivalents and substitutions within the scope of the thought and technology of the present invention.
[0021] Hereinafter, the present invention will be described in more detail.
[0022] Polyethylene composition
[0023] According to one aspect of the present invention, there is provided a polyethylene composition comprising at least one ethylene-α-olefin copolymer, wherein the main chain weight average molecular weight (Mw) of a high crystalline fraction eluted above 90° C. from a cross fractionation chromatography (CFC) analysis of the polyethylene composition is main,T≥90℃ ) is less than 150000 g / mol.
[0024] In addition, the "parts by weight" used in this article refers to a relative concept of the ratio of the weight of the remaining materials based on the weight of a specific material. For example, in a mixture containing 50g of material A, 20g of material B and 30g of material C, based on 100 parts by weight of material A, the amounts of material B and C are 40 parts by weight and 60 parts by weight, respectively.
[0025] Meanwhile, "wt%" refers to an absolute concept expressing the weight of a specific material as a percentage based on the total weight. In the above mixture, the contents of materials A, B and C are 50 wt%, 20 wt% and 30 wt%, respectively, based on 100% of the total weight of the mixture.
[0026] In the polyethylene composition of the present invention, a first ethylene-α-olefin copolymer having excellent fluidity to impart stretchability is blended with a second ethylene-α-olefin copolymer having excellent mechanical properties by applying a specific metallocene catalyst to be described below, thereby adjusting the balance between mechanical properties and elongation. Therefore, it has characteristics suitable for manufacturing a biaxially stretched film having high shrinkage resistance, printability and transparency while maintaining mechanical properties, productivity and stretching stability equivalent to or superior to those of conventional materials.
[0027] The polyethylene composition may include, for example, (a) a polyethylene having a density of 0.870 g / cm 3 Up to 0.920g / cm 3 And the melt index (MI 2.16 , 190°C, 2.16 kg load) of 3.0 g / 10 minutes to 10.0 g / 10 minutes of the first ethylene-alpha olefin copolymer; and (b) a density of 0.930 g / cm 3 Up to 0.960g / cm3 And the melt index (MI 2.16 , 190°C, 2.16 kg load) of 0.2 g / 10 min to 2.0 g / 10 min of the second ethylene-α-olefin copolymer, these materials are respectively prepared by specific metallocene catalysts.
[0028] In particular, the polyethylene composition of one embodiment of the present invention may include the first and second ethylene-α-olefin copolymers in a specific composition, and thus may have desired crystallinity characteristics, and the main chain weight average molecular weight (Mw) of a high crystalline fraction eluted at 90° C. or above from a cross fractionation chromatography (CFC) analysis of the polyethylene composition may be 0.1% to 0.2%. main,T≥90℃ ) is within a specific range. More specifically, the polyethylene composition of this embodiment may exhibit partial crystallinity, which includes a crystalline part having a lamellar structure and an amorphous part between the crystalline parts. These favorable crystalline characteristics of the polyethylene composition (i.e., the molar ratio contained in the amorphous part connected between the layers) may affect physical properties such as the elasticity of the polyethylene composition.
[0029] According to the aforementioned favorable crystallization characteristics, the polyethylene composition of one embodiment of the present invention can have excellent tensile properties and tensile stability. Therefore, when the polyethylene composition is manufactured into a biaxially oriented film, it can exhibit excellent mechanical properties and transparency.
[0030] In a more specific example, the main chain weight average molecular weight (Mw) of the high crystalline fraction eluted at above 90° C. from the cross fractionation chromatography (CFC) analysis of the polyethylene composition of the above embodiment is main,T≥90℃ ) may be 150,000 g / mol or less, or 50,000 g / mol to 150,000 g / mol.
[0031] Preferably, the main chain weight average molecular weight (Mw) of the high crystalline fraction is 200 μg / cm2, which is about 100 μg / cm2, and about 200 μg / cm2, in terms of improving the stress relaxation rate of the polyethylene composition, thereby quickly stabilizing the film during stretching and reducing shrinkage. main,T≥90℃ ) may be 140000 g / mol or less, or 135000 g / mol or less, or 130000 g / mol or less, or 125000 g / mol or less, or 120000 g / mol or less, or 118000 g / mol or less, or 115000 g / mol or less. However, in terms of maintaining excellent mechanical properties of the film, the main chain weight average molecular weight (Mw main,T≥90℃ ) can be 6000 g / mol or more, or 7000 g / mol or more, or 80000 g / mol or more, or 90000 g / mol or more, or 100000 g / mol or more, or 105000 g / mol or more, or 110000 g / mol or more.
[0032] In addition, the content ratio (TREF) of the high crystalline fraction eluted at 90° C. or higher from cross fractionation chromatography (CFC) analysis of the polyethylene composition is T≥90℃ ) is 50% or more or 50% or more and 95% or less of the total weight of all eluted fractions. Specifically, the content ratio of the high crystalline fraction (TREF T≥90℃ ) can be more than 50.2%, more than 50.5% or more than 50.9% of the total weight of all eluted fractions, and if necessary, can be less than 90%, less than 85%, less than 80%, less than 75%, less than 70%, or less than 65% of the total weight of all eluted fractions.
[0033] The content ratio of the low-middle crystalline fraction eluting at less than 90° C. (TREF) of the polyethylene composition from the cross fractionation chromatography (CFC) analysis of the polyethylene composition T<90℃ ) is less than 50% of the total weight of all eluted fractions, or more than 5% and less than 50%. Specifically, the content ratio of the middle and low crystalline fractions (TREF T<90℃ ) can be less than 49.8%, or less than 49.5%, or less than 49.1% of the total weight of all eluted fractions, and if necessary, can be more than 10%, or more than 15%, or more than 20%, or more than 25%, or more than 30%, or more than 35% of the total weight of all eluted fractions.
[0034] In the present invention, a specific test method related to cross fractionation chromatography (CFC) is as described in Test Example 2 to be described below. However, cross fractionation chromatography (CFC) is not limited thereto and may be measured by other methods known in the art to which the present invention pertains.
[0035] For example, cross fractionation chromatography (CFC) can be performed on the polyethylene composition of one embodiment of the present invention, including temperature rising elution fractionation (TREF) analysis and GPC-IR analysis in the following manner. The main chain weight average molecular weight (Mw main,T≥90℃ ), the content ratio of the high crystalline fraction eluted above 90°C (TREF T≥90℃ ) and the content ratio of the medium and low crystalline fraction eluted at less than 90°C (TREF T<90℃ ).
[0036] Cross Fractionation Chromatography (CFC) Measurement Conditions (including TREF and GPC-IR analysis)
[0037] -Analysis equipment: Polymer Char CFC (Detector: Integrated detector IR5MCT)
[0038] -Sample preparation and injection: 32 mg of the polyethylene composition was added to a 10 mL vial and placed in an autosampler. Then, 8 mL of 1,2,4-trichlorobenzene (TCB) was added, dissolved at 160°C for 90 minutes, extracted after nitrogen purge, and then injected into a temperature rising elution fractionation column (TREF column).
[0039] - Crystallization: After the temperature of the sample previously injected into the TREF column was adjusted to 100°C, cooling from 100°C to 35°C was performed at 0.5°C / min.
[0040] - Temperature Rising Elution Fractionation (TREF) analysis: A previously crystallized sample is heated from 35°C to 120°C at intervals of 1°C and fixed. Then, the fractions eluted at each temperature within 25 minutes are analyzed. Specifically, it is possible to extract and analyze at 35°C for 25 minutes, then extract and analyze after increasing the temperature at intervals of 1°C, and finally extract and analyze at 120°C for 25 minutes.
[0041] -GPC-IR analysis: The fractions eluted at each temperature in the previous TREF analysis were transferred to the GPC column of the GPC (PL-GPC220) apparatus, the molecular weights of the eluted molecules were measured, and the number of short chain branches (scb) of the molecules eluted at each temperature was measured using a PerkinElmer Spectrum 100 FT-IR connected to the GPC (PL-GPC220).
[0042] -Main chain weight average molecular weight (Mw main,T≥90℃ ): The weight average molecular weight (Mw) of the main chain (excluding short chain branches) of the high crystalline fraction eluted at 90°C or above of the polyethylene composition as confirmed by CFC analysis of the polyethylene composition. main,T≥90℃ The value of , g / mol) is calculated by the following Equation 1.
[0043] [Equation 1]
[0044]
[0045] In Equation 1, M T,i and C T,i are the weight average molecular weight (g / mol) and concentration of each fraction eluted at each measurement temperature, respectively, obtained by the above-mentioned CFC analysis of the polyethylene composition.
[0046] n scb T,i is the number of short chain branches (scb) of each fraction eluted at each measurement temperature, respectively, obtained by the above CFC analysis of the polyethylene composition, and
[0047] M scbis the weight average molecular weight (g / mol) of the short chain branch (scb) of each fraction eluted at each measurement temperature, respectively, obtained by the above-mentioned CFC analysis of the polyethylene composition.
[0048] Specifically, the content ratio of the high crystalline fraction (TREF T≥90℃ ) is the content ratio of the high crystalline fraction eluted at above 90° C. (TREF) calculated as a percentage (%) based on the total weight of all eluted fractions of the polyethylene composition obtained by the above CFC analysis T≥90℃ ). The content ratio of the medium and low crystalline fractions (TREF) of the polyethylene composition T<90℃ ) is the content ratio of the medium and low crystalline fraction eluted at less than 90° C. (TREF) calculated as a percentage (%) based on the total weight of all eluted fractions of the polyethylene composition obtained by the above CFC analysis T<90℃ ).
[0049] At the same time, the relaxation time (RT) of the polyethylene component at 120 °C 120℃ ) is 4.0 seconds or less, or 0.02 seconds or more and 4.0 seconds or less. Preferably, the relaxation time (RT) at 120° C. is 0.1 seconds or less, or 0.02 seconds or more and 4.0 seconds or less, in terms of improving the stress relaxation rate so as to quickly stabilize the film during stretching and reduce shrinkage. 120℃ ) may be 3.8 seconds or less, or 3.5 seconds or less, or 3.2 seconds or less, or 3.0 seconds or less, or 2.5 seconds or less. However, in terms of maintaining the excellent mechanical properties of the film, the relaxation time (RT) at 120°C is preferably 120℃ ) can be 0.1 seconds or more, or 0.5 seconds or more, or 1.0 seconds or more, or 1.2 seconds or more, or 1.5 seconds or more, or 1.8 seconds or more, or 2.0 seconds or more.
[0050] The relaxation time of the polyethylene composition can be obtained in the following manner: using a rotational rheometer to measure the viscosity of the polyethylene composition under various temperatures and an angular frequency of 0.05rad / second to 500rad / second, and then using a specific cross model to calculate the relaxation time (seconds) of the polyethylene composition. Alternatively, the relaxation time (seconds) of the polyethylene composition at a specific temperature can be estimated by an Arrhenius curve according to the value of the relaxation time (seconds) under various temperature conditions as described above. For example, the specific measurement method of the relaxation time of the polyethylene composition is as described in Test Example 2 described below. However, the measurement method of the relaxation time of the polyethylene composition is not limited thereto, and can be measured by other methods known in the art to which the present invention belongs.
[0051] At the same time, the density of the polyethylene composition can be 0.928 g / cm 3 Above 0.942g / cm 3Preferably, the density can be 0.929 g / cm 3 Above, 0.930g / cm 3 Above or 0.931g / cm 3 Above, and can be 0.940g / cm 3 Below, 0.939g / cm 3 Below, 0.938g / cm 3 the following.
[0052] In addition, the melt index (MI) of the polyethylene composition 2.16 , 190°C, 2.16 kg load) can be 0.6 g / 10 min to 1.5 g / 10 min. Preferably, the melt index (MI 2.16 , 190°C, 2.16 kg load) can be 0.65 g / 10 min or more, 0.7 g / 10 min or more, or 0.75 g / 10 min or more, and can be 1.4 g / 10 min or less, 1.3 g / 10 min or less, or 1.2 g / 10 min or less.
[0053] In the present invention, the melt index (MI 2.16 ) can be measured according to ASTM D 1238 (Condition E, 190°C, 2.16 kg) of the American Society for Testing and Materials at 190°C under a load of 2.16 kg. For example, the melt index (MI 2.16 ) as described in Test Examples 1 and 2 which will be described below.
[0054] In addition, the polyethylene composition may have a number average molecular weight (Mn) of 25,000 g / mol or more, or from 25,000 g / mol to 500,000 g / mol; and a weight average molecular weight (Mw) of 105,000 g / mol or more, or from 105,000 g / mol to 1,000,000 g / mol; and a molecular weight distribution (Mw / Mn) of 5.0 or less, or from 0.5 to 5.0.
[0055] Preferably, the molecular weight distribution (Mw / Mn) of the polyethylene composition may be 4.8 or less, or 4.5 or less, or 4.3 or less, or 4.0 or less, or 3.8 or less. In addition, the molecular weight distribution (Mw / Mn) may be 1.0 or more, or 1.2 or more, or 1.5 or more, or 1.8 or more, or 2.0 or more, or 2.5 or more, or 2.8 or more, or 3.0 or more.
[0056] In the present invention, weight average molecular weight (Mw) and number average molecular weight (Mn) are values converted from standard polystyrene measured by GPC (gel permeation chromatography). However, weight average molecular weight is not limited thereto and can be measured by other methods known in the art. As an example, the measuring method of weight average molecular weight (Mw) and number average molecular weight (Mn) is as described in Test Examples 1 and 2 described hereinafter.
[0057] For example, the weight average molecular weight (Mw) and the number average molecular weight (Mn) can be measured using gel permeation chromatography (GPC, manufactured by Water) according to ASTM D6474 of the American Society for Testing and Materials. Specifically, the PL-GPC220 manufactured by Waters can be used as a gel permeation chromatography (GPC) instrument, and a Polymer Laboratories PLgel MIX-B 300mm long column can be used. The evaluation temperature can be 160 ° C, and 1,2,4-trichlorobenzene can be used as a solvent at a flow rate of 1mL / min. Each polyethylene sample can be dissolved in 1,2,4-trichlorobenzene containing 0.0125% of BHT at 160 ° C for 10 hours for pretreatment, and a sample with a concentration of 10mg / 10mL can be supplied in an amount of 200 microliters (μL). The calibration curve formed using polystyrene standards can be used to obtain Mw and Mn values. Nine polystyrene standards were used with molecular weights of 2000 g / mol, 10000 g / mol, 30000 g / mol, 70000 g / mol, 200000 g / mol, 700000 g / mol, 2000000 g / mol, 4000000 g / mol, and 10000000 g / mol.
[0058] In addition, the polyethylene composition may have a melting point (Tm) of 125° C. to 129° C., a crystallization temperature (Tc) of 112° C. to 115° C., and a degree of crystallinity (Xc) of 35% to 48%.
[0059] In the present invention, the melting point Tm, the crystallization temperature Tc and the crystallinity Xc can be measured using a differential scanning calorimeter (DSC). For example, the melting point Tm, the crystallization temperature Tc and the crystallinity Xc are measured as described in Test Example 2 described below.
[0060] For example, the melting point (Tm), crystallization temperature (Tc) and crystallinity (Xc) of the polyethylene composition can be measured using a differential scanning calorimeter (DSC, equipment name: DSC Q20, manufacturer: TA instrument). Specifically, the polyethylene composition is heated to 180°C at 10°C / min (cycle 1), isothermally maintained at 180°C for 5 minutes, cooled to 0°C at 10°C / min, isothermally maintained at 30°C for 5 minutes, and then heated to 180°C at 10°C / min again (cycle 2). In the DSC curve obtained above, the temperature at the maximum point of the endothermic peak is measured as the melting point (Tm, °C), and the temperature at the maximum point of the exothermic peak is measured as the crystallization temperature (Tc, °C). At this time, the melting point (Tm) and the crystallization temperature (Tc) are shown as the measurement results in cycle 2 of the second heating and cooling.
[0061] In addition, the heat of fusion ΔHm is obtained by calculating the area of the melting peak in the second cycle of heating and cooling 2, and the crystallinity (Xc) is obtained by dividing ΔHm by H 0 m=293.6 J / g (theoretical value when the crystallinity is 100%).
[0062] Meanwhile, the polyethylene composition of one embodiment of the present invention contains the first ethylene-α olefin copolymer (a) in an amount greater than 0 and 40 wt% or less, and contains the second ethylene-α olefin copolymer (b) in an amount greater than 60 wt% and less than 100 wt%.
[0063] Preferably, the content of the first ethylene-α-olefin copolymer (a) may be 5 wt% or more, 10 wt% or more, or 15 wt% or more, and may be 38 wt% or less, 35 wt% or less, or 30 wt% or less.
[0064] Furthermore, the content of the second ethylene-α-olefin copolymer (b) may be 62% by weight or more, 65% by weight or more, or 70% by weight or more, and may be 85% by weight or less, 90% by weight or less, or 95% by weight or less.
[0065] When the first and second ethylene-α olefin copolymers are combined in appropriate amounts, the composition of one embodiment may satisfy an appropriate crystal structure, and thus may satisfy all of the above-described excellent physical properties.
[0066] In the polyethylene composition, the first and second ethylene-alpha olefin copolymers can each be a copolymer of ethylene and an alpha olefin with 3 to 20 carbon atoms. In a more specific embodiment, it can be a copolymer of ethylene and 1-butene, 1-hexene or 1-octene. In a specific embodiment, these first and second ethylene-alpha olefin copolymers can be the same or different from each other. For example, the first ethylene-alpha olefin copolymer (a) can be an ethylene / 1-octene copolymer and the second ethylene-alpha olefin copolymer (b) can be an ethylene / 1-hexene copolymer.
[0067] First ethylene-α-olefin copolymer (a)
[0068] In the polyethylene composition of one embodiment of the present invention, the first ethylene-α-olefin copolymer (a) has excellent fluidity, thereby having excellent tensile stability and shrinkage resistance, and can impart properties suitable for producing a biaxially stretched film.
[0069] Specifically, the density of the first ethylene-α-olefin copolymer (a) is 0.870 g / cm 3 Up to 0.920g / cm 3 And the melt index (MI 2.16 , 190°C, 2.16 kg load) is 3.0 g / 10 minutes to 10.0 g / 10 minutes.
[0070] Preferably, the density of the first ethylene-α-olefin copolymer (a) may be 0.880 g / cm 3 Above, 0.890g / cm 3 Above or 0.895g / cm 3 Above, and can be 0.915g / cm 3 Below, 0.910g / cm 3 Below or 0.905g / cm 3 the following.
[0071] In addition, the melt index (MI) of the first ethylene-α-olefin copolymer (a) 2.16 , 190°C, 2.16 kg load) can be 3.5 g / 10 minutes or more, 4.0 g / 10 minutes or more, or 4.5 g / 10 minutes or more, and can be 9.0 g / 10 minutes or less, 8.0 g / 10 minutes or less, or 7.0 g / 10 minutes or less.
[0072] The first ethylene-α-olefin copolymer (a) may have a number average molecular weight (Mn) of 20,000 g / mol or more, or 20,000 g / mol or more and 50,000 g / mol or less, a weight average molecular weight (Mw) of 60,000 g / mol or more and 95,000 g / mol or more, and a molecular weight distribution (Mw / Mn) of 2.0 or more and less than 3.5.
[0073] Preferably, the number average molecular weight (Mn) of the first ethylene-α-olefin copolymer (a) may be 22,000 g / mol or more, 25,000 g / mol or more, or 28,000 g / mol or more, and may be 34,000 g / mol or less, 33,000 g / mol or less, or 32,000 g / mol or less.
[0074] The weight average molecular weight (Mw) of the first ethylene-α-olefin copolymer (a) may be 62,000 g / mol or more, 64,000 g / mol or more, or 65,000 g / mol or more, and may be 90,000 g / mol or less, 80,000 g / mol or less, or 70,000 g / mol or less.
[0075] Furthermore, the molecular weight distribution (Mw / Mn) of the first ethylene-α-olefin copolymer (a) may be 2.1 or more, 2.2 or more, or 2.3 or more, and may be 3.2 or less, 3.0 or less, 2.8 or less, or 2.5 or less.
[0076] The first ethylene-α-olefin copolymer (a) may have at least one of the above-mentioned physical properties, and may have all of the above-mentioned physical properties to exhibit excellent mechanical strength.
[0077] Here, the methods for measuring the various physical properties of the first ethylene-α-olefin copolymer (a) are the same as those described previously for the polyethylene composition, and thus detailed descriptions are omitted.
[0078] The first ethylene-α-olefin copolymer (a) may comprise, together with ethylene, at least one α-olefin selected from the group consisting of 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, and mixtures thereof.
[0079] Preferably, the first ethylene-α-olefin copolymer (a) may be an ethylene / 1-octene copolymer.
[0080] When the first ethylene-α-olefin copolymer (a) is the above copolymer, the above physical properties can be easily achieved. However, the type of the first ethylene-α-olefin copolymer (a) is not limited thereto, and various types known in the art can be used as long as it can exhibit the above physical properties.
[0081] Meanwhile, the first ethylene-α-olefin copolymer (a) may be prepared in the presence of a metallocene catalyst.
[0082] Specifically, the first ethylene-α-olefin copolymer (a) may be prepared by copolymerizing ethylene and a comonomer in the presence of a catalyst composition comprising a metallocene compound represented by the following Chemical Formula 1:
[0083] [Chemical formula 1]
[0084]
[0085] In Chemical Formula 1,
[0086] M 1 It is a Group 4 transition metal;
[0087] X 1 and X 2 are the same as or different from each other and are each independently a halogen, a nitro group, an amide group, a phosphine group, a phosphide group, a C1 to C30 hydrocarbon group, a C1 to C30 hydrocarbonoxy group, a C2 to C30 hydrocarbonoxy hydrocarbon group, -SiH3, a C1 to C30 hydrocarbon (oxy) silyl group, a C1 to C30 sulfonate group or a C1 to C30 sulfone group;
[0088] Z is -O-, -S-, -NR a -, or -PR a -;
[0089] R a is any one of hydrogen, C1 to C20 hydrocarbon group, C1 to C20 hydrocarbon (oxy) silyl group and C1 to C20 silyl hydrocarbon group;
[0090] T is
[0091] T 1 is C, Si, Ge, Sn or Pb,
[0092] Q 1 and Q 2 are the same as or different from each other and are each independently hydrogen, C1 to C30 hydrocarbon group, C1 to C30 hydrocarbon oxy group, C2 to C30 hydrocarbon oxy hydrocarbon group, -SiH3, C1 to C30 hydrocarbon (oxy) silyl group, halogenated C1 to C30 hydrocarbon group and -NR b R c Any of the following;
[0093] R b and R c Each independently represents at least one of hydrogen and a C1 to C30 hydrocarbon group, or are connected to each other to form an aliphatic ring or an aromatic ring; and
[0094] C 1 is any one of the ligands represented by the following chemical formulas 1a to 1d,
[0095] [Chemical formula 1a]
[0096]
[0097] [Chemical formula 1b]
[0098]
[0099] [Chemical formula 1c]
[0100]
[0101] [Chemical formula 1d]
[0102]
[0103] In Chemical Formulae 1a to 1d,
[0104] Y is O or S, and
[0105] R 1 To R 6 are the same as or different from each other, and are each independently any one of hydrogen, a C1 to C30 hydrocarbon group, and a C1 to C30 hydrocarbonoxy group.
[0106] Unless otherwise specified herein, the following terms may be defined as follows.
[0107] The hydrocarbyl group is a monovalent functional group in the form of removing one hydrogen from a hydrocarbon, and may include alkyl, alkenyl, alkynyl, aryl, arylalkyl, arylalkenyl, arylalkynyl, alkylaryl, alkenylaryl, alkynylaryl, etc. The C1 to C30 hydrocarbyl group may be a C1 to C20 hydrocarbyl group or a C1 to C10 hydrocarbyl group. For example, the hydrocarbyl group may be a straight chain, branched or cyclic alkyl group. More specifically, the C1 to C30 hydrocarbyl group may be a straight chain, branched or cyclic alkyl group such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, n-hexyl, n-heptyl and cyclohexyl; or an aryl group such as phenyl, biphenyl, naphthyl, anthracenyl, phenanthrenyl or fluorenyl. In addition, it may be an alkylaryl group such as methylphenyl, ethylphenyl, methylbiphenyl and methylnaphthyl or an arylalkyl group such as phenylmethyl, phenylethyl, biphenylmethyl and naphthylmethyl. It may also be an alkenyl group such as allyl, vinyl, propenyl, butenyl and pentenyl.
[0108] Hydrocarbyl is a functional group in which a hydrocarbon group is bonded to oxygen. Specifically, the C1 to C30 hydrocarbyl may be a C1 to C20 hydrocarbyl or a C1 to C10 hydrocarbyl. For example, the hydrocarbyl may be a straight chain, branched or cyclic alkyl. More specifically, the C1 to C30 hydrocarbyl may be a straight chain, branched or cyclic alkoxy such as methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy, n-pentoxy, n-hexoxy, n-heptyloxy and cyclohexyloxy; or an aryloxy group such as phenoxy and naphthoxy.
[0109] Hydrocarbyl is a functional group in which at least one hydrogen of a hydrocarbon group is replaced by at least one hydrocarbonoxy group. Specifically, the C2 to C30 hydrocarbyl may be a C2 to C20 hydrocarbyl or a C2 to C15 hydrocarbyl. For example, the hydrocarbyl may be a straight chain, branched or cyclic alkyl. More specifically, the C2 to C20 hydrocarbyl may be a straight chain, branched or cyclic alkoxyalkyl such as methoxymethyl, methoxyethyl, ethoxymethyl, isopropoxymethyl, isopropoxyethyl, isopropoxyhexyl, tert-butoxymethyl, tert-butoxyethyl and tert-butoxyhexyl; or an aryloxyalkyl, such as phenoxyhexyl.
[0110] Hydrocarbyl (oxy) silyl is a functional group in which one to three hydrogens of -SiH3 are replaced by one to three hydrocarbyl or hydrocarbyloxy groups. Specifically, C1 to C30 hydrocarbyl (oxy) silyl can be C1 to C20, C1 to C15, C1 to C10 or C1 to C5 hydrocarbyl (oxy) silyl. More specifically, C1 to C30 hydrocarbyl (oxy) silyl can be, for example, the following alkyl silyls: methyl silyl, dimethyl silyl, trimethyl silyl, dimethyl ethyl silyl, diethyl methyl silyl or dimethyl propyl silyl; alkoxy silyl, for example, methoxy silyl, dimethoxy silyl, trimethoxy silyl or dimethoxy ethoxy silyl; or alkoxy alkyl silyl, for example, methoxy dimethyl silyl, diethoxy methyl silyl or dimethoxy propyl silyl.
[0111] C1 to C20 silyl hydrocarbyl is a functional group in which at least one hydrogen of a hydrocarbyl is replaced by a silyl group. Silyl can be -SiH3 or a hydrocarbon (oxy) silyl group. Specifically, C1 to C20 silyl hydrocarbyl can be a C1 to C15 silyl hydrocarbyl or a C1 to C10 silyl hydrocarbyl. More specifically, C1 to C20 silyl hydrocarbyl can be a silylalkyl group, such as -CH2-SiH3; an alkylsilylalkyl group, such as methylsilylmethyl, methylsilylethyl, dimethylsilylmethyl, trimethylsilylmethyl, dimethylethylsilylmethyl, diethylmethylsilylmethyl or dimethylpropylsilylmethyl; or an alkoxysilylalkyl group, such as dimethylethoxysilylpropyl.
[0112] The halogen may be fluorine (F), chlorine (Cl), bromine (Br) or iodine (I).
[0113] Sulfonate groups may have -O-SO2-R d The structure of R d It may be a C1 to C30 hydrocarbon group. Specifically, the C1 to C30 sulfonate group may be a methanesulfonate group, a phenylsulfonate group, or the like.
[0114] C1 to C30 sulfone groups have -R e’ -SO2-R e " structure, and R e’ and R e " may be the same as or different from each other, and may each independently be any one of C1 to C30 hydrocarbon groups. Specifically, the C1 to C30 sulfone group may be methylsulfonylmethyl, methylsulfonylpropyl, methylsulfonylbutyl, phenylsulfonylpropyl, and the like.
[0115] In the present invention, "two adjacent substituents are linked to each other to form an aliphatic ring or an aromatic ring" means that the atoms of the two substituents and the atoms bonded to the two substituents are linked to each other to form a ring. Specifically, -NR b R c or -NR b’ R c’ R b and R c or R b’ and R c’ Examples of groups connected to each other to form an aliphatic ring include piperidinyl, -NR b R c or -NR b’ R c’ R b and R c or R b’ and R c’ Examples of groups linked to each other to form an aromatic ring include pyrrolyl.
[0116] The Group 4 transition metal may be titanium (Ti), zirconium (Zr), hafnium (Hf) or (Rf), and may be more specifically titanium (Ti), zirconium (Zr), and hafnium (Hf). More specifically, it may be zirconium (Zr) or hafnium (Hf), but the present invention is not limited thereto.
[0117] In addition, the Group 13 element may be boron (B), aluminum (Al), gallium (Ga), indium (In), or thallium (Tl), and may be specifically boron (B) or aluminum (Al), but the present invention is not limited thereto.
[0118] The above-mentioned substituents may be optionally substituted with one or more substituents selected from the group consisting of hydroxyl; halogen; hydrocarbon group; hydrocarbonoxy group; hydrocarbon group or hydrocarbonoxy group containing at least one heteroatom among heteroatoms of Groups 14 to 16; silyl group; hydrocarbon(oxy)silyl group; phosphine group; phosphide group; sulfonate group; and sulfone group within the range of exhibiting the same or similar effects as the desired effects.
[0119] In the present invention, Represents a bond to another substituent.
[0120] Specifically, in Chemical Formula 1, Z is -NR a -, where R a It can be a C1 to C10 hydrocarbon group. a It may be a linear or branched C1 to C6 alkyl group. More specifically, it may be a tert-butyl group.
[0121] In chemical formula 1, T is in,
[0122] T 1 is carbon (C) or silicon (Si), Q 1 and Q 2 can each independently be hydrogen, a C1 to C30 hydrocarbon group, or a C1 to C30 hydrocarbonoxy group. 1 and Q 2 Each of Q may be a C1 to C10 hydrocarbon group or a C2 to C12 hydrocarbonoxy hydrocarbon group. 1 and Q 2 Each of Q and Q may be a C1 to C6 alkyl group, or a C1 to C6 alkyl group substituted with a C1 to C6 alkoxy group. 1 and Q 2 may be independently hydrogen, methyl, ethyl or tert-butyl substituted hexyl. More specifically, T 1 is silicon (Si); Q 1 and Q 2 is a hexyl group substituted with a methyl group or a tert-butyl group. More specifically, T 1 is silicon (Si); Q 1 and Q 2 is methyl, or Q 1 and Q 2 One of the is methyl and the other is tert-butyl substituted hexyl.
[0123] Specifically, the metallocene compound represented by Chemical Formula 1 may be a compound represented by any one of the following Chemical Formulas 1-1 to 1-4.
[0124] [Chemical formula 1-1]
[0125]
[0126] [Chemical formula 1-2]
[0127]
[0128] [Chemical formula 1-3]
[0129]
[0130] [Chemical formula 1-4]
[0131]
[0132] In Chemical Formulas 1-1 to 1-4, M 1 , X 1 , X 2 , R a , T 1 , Q 1 , Q 2 , Y and R 1 To R 6 The same as defined in Chemical Formula 1.
[0133] In Chemical Formula 1, R 1 To R 4 may each be hydrogen or a C1 to C10 hydrocarbon group, and R 5 and R 6 Each of R 1 To R 4 may each be hydrogen or a C1 to C10 alkyl group, and R 5 and R 6 may each be a C1 to C10 alkyl group. More specifically, R 1 To R 4 may each be hydrogen or methyl, and R 5 and R 6 It may be methyl.
[0134] In Chemical Formula 1, M 1 It may be titanium (Ti), zirconium (Zr), or hafnium (Hf), and is preferably titanium (Ti).
[0135] Furthermore, in Chemical Formula 1, X 1 and X 2 Each may be halogen, C1 to C10 alkyl or C1 to C6 alkyl, and specifically chlorine or methyl.
[0136] In addition, in Chemical Formula 1, the metallocene compound may be represented by one of the following structural formulas.
[0137]
[0138] The metallocene compound represented by the above structural formula can be synthesized by applying known reactions, and a more specific synthesis method can be understood with reference to the Examples and Synthesis Examples.
[0139] As described above, the transition metal compound represented by Chemical Formula 1 used in the present invention controls the degree of introduction of the α-olefin monomer during copolymerization due to the structural characteristics of the catalyst and exhibits the above density, and thus is excellent in fluidity and drawing processability.
[0140] In the present invention, the polymerization reaction can be carried out by continuously polymerizing ethylene and α-olefin monomers while continuously introducing hydrogen in the presence of a catalyst composition containing at least one transition metal compound represented by Chemical Formula 1. Specifically, it can be carried out while introducing hydrogen at 5 to 100 cc / min.
[0141] Hydrogen inhibits the rapid reaction of the transition metal compound at the initial stage of polymerization and serves to terminate the polymerization reaction. Therefore, by using hydrogen and adjusting its amount, an ethylene / α-olefin copolymer having a narrow molecular weight distribution can be efficiently produced.
[0142] For example, hydrogen can be introduced under the following conditions: 5cc / min or more, 7cc / min or more, 10cc / min or more, 15cc / min or more, or 19cc / min or more, and can be 100cc / min or less, 50cc / min or less, 45cc / min or less, 35cc / min or less, or 29cc / min or less. When added under the above conditions, the ethylene / α-olefin copolymer to be produced can achieve the physical properties of the present invention.
[0143] When hydrogen is introduced at less than 5 cc / min, the polymerization reaction cannot be terminated uniformly, making it difficult to prepare an ethylene / α-olefin copolymer having desired physical properties. When hydrogen is introduced at more than 100 cc / min, the reaction is terminated too quickly, so an ethylene / α-olefin copolymer having a very low molecular weight can be produced.
[0144] In addition, the polymerization reaction can be carried out at 100° C. to 200° C., and by adjusting the polymerization temperature and the amount of hydrogen input, the crystallinity distribution and molecular weight distribution of the ethylene / α-olefin copolymer can be more easily controlled. Specifically, the polymerization reaction can be carried out at 100° C. to 200° C., 120° C. to 180° C., 130° C. to 170° C., or 140° C. to 160° C., but is not limited thereto.
[0145] In the present invention, a co-catalyst may be further used in the catalyst composition to activate the transition metal compound of Chemical Formula 1. The co-catalyst is an organic metal compound containing a Group 13 metal, and may specifically include one or more selected from the following Chemical Formulas 2 to 4.
[0146] [Chemical formula 2]
[0147] R8-[Al(R7)-O] n -R9
[0148] In the chemical formula,
[0149] R7, R8 and R9 are each independently hydrogen, halogen, C 1-20 Hydrocarbon or halogenated C 1-20 hydrocarbon group, and
[0150] n is an integer greater than 2,
[0151] [Chemical formula 3]
[0152] D(R 10 )3
[0153] In chemical formula 3,
[0154] D is aluminum or boron, and
[0155] R 10 are independently halogen, C 1-20 Hydrocarbon, C 1-20 Hydroxyl or halogenated C 1-20 Hydrocarbon,
[0156] [Chemical formula 4]
[0157] [LH] + [W(A)4] - or [L] + [W(A)4] -
[0158] In chemical formula 4,
[0159] L is a neutral or cationic Lewis base,
[0160] H is a hydrogen atom,
[0161] W is a Group 13 element, and
[0162] A is independently any of the following: C 1-20 Hydrocarbon; C 1-20 Hydrocarbyloxy; and one or more hydrogen atoms of these substituents are selected from halogen, C 1-20 Hydroxyl and C 1-20 A substituent in which the hydrocarbyl(oxy)silyl group is substituted with one or more substituents.
[0163] Specifically, in Chemical Formula 4, [LH] + It is a Bronsted acid.
[0164] For example, [LH] +is trimethylammonium; triethylammonium; tripropylammonium; tributylammonium; diethylammonium; trimethylphosphonium; or triphenylphosphonium, wherein [L] + It is N,N-diethylanilinium; or triphenylcarbonium.
[0165] In addition, in Chemical Formula 4, W may be B 3+ or Al 3+ .
[0166] The compound represented by Chemical Formula 2 may function as an alkylating agent and an activating agent, the compound represented by Chemical Formula 3 may function as an alkylating agent, and the compound represented by Chemical Formula 4 may function as an activating agent.
[0167] More specifically, the compound of Chemical Formula 2 may be an alkylaluminoxane compound in which repeating units are bonded into a linear, cyclic or network shape, and specific examples thereof may include methylaluminoxane (MAO), ethylaluminoxane, isobutylaluminoxane or tert-butylaluminoxane, etc. Non-limiting examples of the compound represented by Chemical Formula 4 may include methylaluminoxane, ethylaluminoxane, isobutylaluminoxane, tert-butylaluminoxane, etc.
[0168] In addition, non-limiting examples of the compound represented by Chemical Formula 3 may include trimethylaluminum, triethylaluminum, triisobutylaluminum, tripropylaluminum, tributylaluminum, dimethylaluminum chloride, triisopropylaluminum, tri-sec-butylaluminum, tricyclopentylaluminum, tripentylaluminum, triisopentylaluminum, trihexylaluminum, trioctylaluminum, ethyldimethylaluminum, methyldiethylaluminum, triphenylaluminum, tri-p-tolylaluminum, dimethylmethoxyaluminum, dimethylethoxyaluminum, and the like.
[0169] In addition, non-limiting examples of the compound represented by Chemical Formula 4 may include trimethylammonium tetrakis(pentafluorophenyl)borate, triethylammonium tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium n-butyltris(pentafluorophenyl)borate, N,N-dimethylanilinium benzyltris(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(4-(tert-butyldimethylsilyl)-2,3,5,6-tetrafluorophenyl)borate, N,N-dimethylanilinium tetrakis(4-(triisopropylsilyl)- 2,3,5,6-tetrafluorophenyl) borate, N,N-dimethylanilinium pentafluorophenoxy tris(pentafluorophenyl) borate, N,N-dimethyl-2,4,6-trimethylanilinium tetrakis(pentafluorophenyl) borate, trimethylammonium tetrakis(2,3,4,6-tetrafluorophenyl) borate, N,N-dimethylanilinium tetrakis(2,3,4,6-tetrafluorophenyl) borate, hexadecyldimethylammonium tetrakis(pentafluorophenyl) borate, N-methyl-N-dodecylanilinium tetrakis(pentafluorophenyl) borate, methyldi(dodecyl)ammonium tetrakis(pentafluorophenyl) borate, etc.
[0170] Among the above compounds, the co-catalyst may be more specifically an alkylaluminoxane compound such as methylaluminoxane.
[0171] The amount of the co-catalyst used can be appropriately adjusted according to the desired physical properties or effects of the mixed supported metallocene catalyst.
[0172] The co-catalyst may be used in an appropriate amount so that activation of the transition metal compound of Chemical Formula 1 can be sufficiently performed. The amount of the co-catalyst used may be appropriately adjusted according to the desired physical properties or effects of the mixed supported metallocene catalyst or the catalyst composition.
[0173] In the present invention, the transition metal compound of Chemical Formula 1 may be used in a state of being supported on a carrier.
[0174] When the transition metal compound of Chemical Formula 1 is loaded on a carrier, the weight ratio of the transition metal compound to the carrier may be 1:10 to 1:1000, more specifically 1:10 to 1:500. When the carrier and the transition metal compound are included within the above weight ratio, an optimal shape may be exhibited. In addition, when the cocatalyst is loaded on a carrier, the weight ratio of the cocatalyst to the carrier may be 1:1 to 1:100, more specifically 1:1 to 1:50. When the cocatalyst and the carrier are included within the above weight ratio, the activity of the catalyst may be improved, and the microstructure of the polymer to be produced may be optimized.
[0175] Meanwhile, the carrier may be silicon dioxide, aluminum oxide, magnesium oxide or a mixture thereof, or may be used in a state containing highly reactive hydroxyl or siloxane groups on its surface by removing moisture from the surface after drying these materials at high temperature. In addition, the carrier dried at high temperature generally contains oxides, carbonates, nitrates, such as Na2O, K2CO3, BaSO4, Mg(NO3)2, etc.
[0176] The drying temperature of the carrier may preferably be about 200° C. to 800° C., more preferably about 300° C. to 600° C., and most preferably about 300 to 400° C. When the drying temperature of the carrier is less than 200° C., surface moisture may react with the co-catalyst due to excessive moisture. When the drying temperature of the carrier is greater than 800° C., pores on the surface of the carrier may be combined to reduce the surface area, and a large amount of hydroxyl groups may be lost on the surface and only siloxane groups may remain, thereby reducing the reaction sites with the co-catalyst, which is not preferred.
[0177] The amount of hydroxyl groups on the surface of the carrier may preferably be 0.1 mmol / g to 10 mmol / g, more preferably 0.5 mmol / g to 5 mmol / g. The amount of hydroxyl groups on the surface of the carrier may be controlled by the preparation method and preparation conditions or drying conditions (e.g., temperature, time, vacuum, spray drying, etc.) of the carrier.
[0178] In addition, an organoaluminum compound is further added during the polymerization reaction to remove moisture from the reactor, and the polymerization reaction can be carried out in the presence of the organoaluminum compound. Specific examples of these organoaluminum compounds may include trialkylaluminum, dialkylaluminum halides, alkylaluminum dihalides, dialkylaluminum hydrides, or alkylaluminum sesquihalides. More specific examples thereof may include Al(C2H5)3, Al(C2H5)2H, Al(C3H7)3, Al(C3H7)2H, Al(i-C4H9)2H, Al(C8H 17 )3、Al(C 12 H 25 )3、Al(C2H5)(C 12 H 25 )2、Al(i-C4H9)(C 12 H 25 )2, Al(i-C4H9)2H, Al(i-C4H9)3, (C2H5)2AlCl, (i-C3H9)2AlCl, (C2H5)3Al2Cl3, etc. These organoaluminum compounds can be added to the reactor continuously, and 0.1 to 10 moles can be added per 1 kg of the reaction medium added to the reactor in order to fully remove moisture.
[0179] In addition, the polymerization pressure may be about 1 Kgf / cm 2 To about 100Kgf / cm 2 , preferably about 1Kgf / cm 2 To about 50Kgf / cm 2 , and more preferably about 5Kgf / cm 2 To about 30Kgf / cm 2 .
[0180] In addition, when the transition metal compound is used in a state supported on a carrier, the transition metal compound can be dissolved or diluted in the following materials and then added: aliphatic hydrocarbon solvents such as pentane, hexane, heptane, nonane, decane and isomers thereof having 5 to 12 carbon atoms, aromatic hydrocarbon solvents such as toluene and benzene, or hydrocarbon solvents substituted with chlorine such as dichloromethane and chlorobenzene. The solvent used herein is preferably used after being treated with a small amount of alkyl aluminum to remove a small amount of water or air as a catalyst poison. A cocatalyst may also be further used.
[0181] The first ethylene-α-olefin copolymer (a) may be prepared by copolymerizing ethylene and an α-olefin using the above-mentioned metallocene catalyst.
[0182] By the above-mentioned preparation method, the first ethylene-α-olefin copolymer (a) having the above-mentioned physical properties can be prepared.
[0183] Second ethylene-α-olefin copolymer (b)
[0184] In the polyethylene composition of the present invention, the second ethylene-α-olefin copolymer (b) having excellent mechanical properties is blended with the above-mentioned first ethylene-α-olefin copolymer (a) to adjust the balance between mechanical properties and elongation. Therefore, it can impart properties suitable for manufacturing a biaxially stretched film having high shrinkage resistance, printability and transparency while maintaining mechanical properties, productivity and tensile stability equivalent to or superior to those of conventional materials.
[0185] Specifically, the density of the second ethylene-α-olefin copolymer (b) is 0.930 g / cm 3 Up to 0.960g / cm 3 And the melt index (MI 2.16 , 190°C, 2.16 kg load) is 0.2 g / 10 min to 2.0 g / 10 min.
[0186] Preferably, the density of the second ethylene-α-olefin copolymer (b) may be 0.935 g / cm 3 Above, 0.938g / cm 3 Above or 0.940g / cm 3 Above, and can be 0.955g / cm 3 Below, 0.950g / cm 3 Below or 0.945g / cm 3 the following.
[0187] In addition, the melt index (MI) of the second ethylene-α-olefin copolymer (b) 2.16 , 190°C, 2.16 kg load) can be 0.2 g / 10 min or more, 0.3 g / 10 min or more, or 0.4 g / 10 min or more, and can be 1.8 g / 10 min or less, 1.5 g / 10 min or less, or 1.2 g / 10 min or less.
[0188] The second ethylene-α-olefin copolymer (b) may have a number average molecular weight (Mn) of 20,000 g / mol or more, or 20,000 g / mol or more and 35,000 g / mol or less, a weight average molecular weight (Mw) of 95,000 g / mol or more and 150,000 g / mol or less, and a molecular weight distribution (Mw / Mn) of 3.5 or more and 4.8 or less.
[0189] Preferably, the number average molecular weight (Mn) of the second ethylene-α-olefin copolymer (b) may be 22,000 g / mol or more, 23,000 g / mol or more, or 25,000 g / mol or more, and may be 33,000 g / mol or less, 32,000 g / mol or less, or 30,000 g / mol or less.
[0190] The weight average molecular weight (Mw) of the second ethylene-α-olefin copolymer (b) may be 100,000 g / mol or more, 105,000 g / mol or more, or 110,000 g / mol or more, and may be 140,000 g / mol or less, 130,000 g / mol or less, or 120,000 g / mol or less.
[0191] Furthermore, the molecular weight distribution (Mw / Mn) of the second ethylene-α-olefin copolymer (b) may be 3.6 or more, or 3.7 or more, or 3.9 or more, or 4.0 or more, and may be 4.7 or less, or 4.5 or less, or 4.3 or less, or 4.2 or less.
[0192] The second ethylene-α-olefin copolymer (b) may have at least one of the above-mentioned physical properties, and may have all of the above-mentioned physical properties to express excellent mechanical strength.
[0193] The methods for measuring the various physical properties of the second ethylene-α-olefin copolymer (b) are the same as those previously described for the polyethylene composition, and thus detailed descriptions are omitted.
[0194] The second ethylene-α-olefin copolymer (b) may comprise, together with ethylene, at least one α-olefin selected from the group consisting of 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, and mixtures thereof.
[0195] The second ethylene-α-olefin copolymer (b) may be an ethylene / 1-hexene copolymer.
[0196] When the second ethylene-α-olefin copolymer (b) is the above copolymer, the above physical properties can be easily achieved. However, the type of the second ethylene-α-olefin copolymer (b) is not limited thereto, and various types known in the art can be used as long as it can exhibit the above physical properties.
[0197] Meanwhile, the second ethylene-α-olefin copolymer (b) may be prepared in the presence of a metallocene catalyst.
[0198] Specifically, the second ethylene-α-olefin copolymer (b) may be prepared by copolymerizing ethylene and a comonomer in the presence of a catalyst composition comprising a first metallocene compound represented by the following Chemical Formula 6 and a second metallocene compound represented by the following Chemical Formula 7 at a molar ratio of 1:1 to 1:8 while introducing hydrogen:
[0199] [Chemical formula 6]
[0200] (Cp 1 R a ) m (Cp 2 R b )M 2 Z 2 3-m
[0201] In Chemical Formula 6,
[0202] M 2 It is a Group 4 transition metal;
[0203] Cp 1 and Cp 2 Each is independently unsubstituted or replaced by C 1-20 Hydrocarbon-substituted cyclopentadienyl;
[0204] R a and R b are the same or different from each other and are each independently C 1-20 Alkyl, C 1-20 Alkoxy, C 2-20 Alkoxyalkyl, C 6-20 Aryl, C 6-20 Aryloxy, C 2-20 Alkenyl, C 7-40 Alkyl aryl, C 7-40 Arylalkyl, C 8-40 Arylene, C 2-20 alkynyl, or a substituted or unsubstituted C containing at least one heteroatom selected from the group consisting of N, O and S 2-20 Heteroaryl, provided that R a and R b At least one of them is not hydrogen;
[0205] Z 2 are independently halogen, C 1-20 Alkyl, C 2-20 Alkenyl, C 7-40 Alkyl aryl, C 7-40 Arylalkyl, C 6-20 Aryl, substituted or unsubstituted C 1-20 Alkylene, substituted or unsubstituted amino, C 2-20 Alkoxyalkyl or C7-40 arylalkoxy; and
[0206] m is 1 or 0;
[0207] [Chemical formula 7]
[0208]
[0209] In Chemical Formula 7,
[0210] M 3 It is a Group 4 transition metal.
[0211] T 2 is carbon, silicon or germanium,
[0212] X 3 and X 4 are the same as or different from each other and are each independently halogen or C 1-20 alkyl,
[0213] R 11 To R 14 are the same as or different from each other and are each independently hydrogen, C 1-20 Alkyl, C 2-20 Alkenyl, C 6-20 Aryl, C 7-20 Alkyl aryl, C 7-20 Arylalkyl, or two or more adjacent R 11 To R 14 are connected to each other to form a substituted or unsubstituted aliphatic ring, a substituted or unsubstituted aromatic ring, or a substituted or unsubstituted heteroaromatic ring containing at least one selected from the group consisting of N, O and S,
[0214] Q 3 and Q 4 are the same or different from each other and are each independently C 1-20 Alkyl, C 2-20 Alkenyl, C 6-30 Aryl or C 2-20 an alkoxyalkyl group, and
[0215] R 15 It is C 1-20 Alkyl, C 2-20 Alkenyl or C 6-30 Aryl.
[0216] Unless otherwise specified herein, the following terms may be defined as follows.
[0217] The halogen may be fluorine (F), chlorine (Cl), bromine (Br) or iodine (I).
[0218] C 1-20The alkyl group may be a linear, branched or cyclic alkyl group. 1-20 The alkyl group can be C 1-15 Straight chain alkyl; C 1-10 Straight chain alkyl; C 1-5 Straight chain alkyl; C 3-20 Branched or cyclic alkyl; C 3-15 Branched or cyclic alkyl; or C 3-10 More specifically, C 1-20 The alkyl group may be methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, cyclohexyl, or the like.
[0219] C 2-20 The alkenyl group may be a straight chain, branched, or cyclic alkenyl group. 2-20 The alkenyl group can be C 2-20 Straight chain alkenyl, C 2-10 Straight chain alkenyl, C 2-5 Straight chain alkenyl, C 3-20 Branched alkenyl, C 3-15 Branched alkenyl, C 3-10 Branched alkenyl, C 5-20 Cyclic alkenyl or C 5-10 More specifically, C 2-20 The alkenyl group may be ethenyl, propenyl, butenyl, pentenyl, cyclohexenyl or the like.
[0220] C 6-20 The aryl group may be a monocyclic, bicyclic or tricyclic aromatic hydrocarbon, and includes a monocyclic or condensed ring aromatic group. 6-20 The aryl group may be phenyl, biphenyl, naphthyl, anthracenyl, phenanthrenyl, fluorenyl or the like.
[0221] C 7-40 The alkylaryl group may be a substituent in which at least one hydrogen of the aryl group is replaced by an alkyl group. 7-40 The alkylaryl group may be methylphenyl, ethylphenyl, n-propylphenyl, isopropylphenyl, n-butylphenyl, isobutylphenyl, tert-butylphenyl, cyclohexylphenyl, or the like.
[0222] C 7-40 The arylalkyl group may include a substituent in which at least one hydrogen of the alkyl group is replaced by an aryl group. 7-40 The arylalkyl group may be benzyl, phenylpropyl, phenylhexyl or the like.
[0223] C 6-20 The aryloxy group may be a phenoxy group, a biphenyloxy group, a naphthoxy group, or the like, but the present invention is not limited thereto.
[0224] C 1-20The alkoxy group may be a methoxy group, an ethoxy group, a phenoxy group, a cyclohexyloxy group, etc., but the present invention is not limited thereto.
[0225] C 2-20 The alkoxyalkyl group is a functional group in which at least one hydrogen of the alkyl group is replaced by an alkoxy group, and specifically, it can be an alkoxyalkyl group, for example, methoxymethyl, methoxyethyl, ethoxymethyl, isopropoxymethyl, isopropoxyethyl, isopropoxyhexyl, tert-butoxymethyl, tert-butoxyethyl, tert-butoxyhexyl, etc., but the present invention is not limited thereto.
[0226] C 1-20 Alkylsilyl or C 1-20 The alkoxysilyl group is a functional group in which 1 to 3 hydrogens of -SiH3 are replaced by 1 to 3 of the above-mentioned alkyl or alkoxy groups, and specifically, it can be an alkylsilyl group, for example, a methylsilyl group, a dimethylsilyl group, a trimethylsilyl group, a dimethylethylsilyl group, a diethylmethylsilyl group or a dimethylpropylsilyl group; an alkoxysilyl group, for example, a methoxysilyl group, a dimethoxysilyl group, a trimethoxysilyl group or a dimethoxyethoxysilyl group; or an alkoxyalkylsilyl group, for example, a methoxydimethylsilyl group, a diethoxymethylsilyl group or a dimethoxypropylsilyl group, but the present invention is not limited thereto.
[0227] C 1-20 The silylalkyl group is a functional group in which at least one hydrogen of an alkyl group is substituted with a silyl group, and specifically, it may be -CH2-SiH3, methylsilylmethyl or dimethylethoxysilylpropyl, etc., but the present invention is not limited thereto.
[0228] The sulfonate group may have a structure of -O-SO2-R', wherein R' may be C 1-20 Specifically, C 1-20 The sulfonate group may be a methanesulfonate group, a phenylsulfonate group, or the like.
[0229] A heteroaryl group is a C 2-20 Heteroaryl, and includes monocyclic or condensed ring heteroaryl. Specifically, it can be xanthine, thioxanthenyl, thienyl, furanyl, pyrrolyl, imidazolyl, thiazolyl, oxazolyl, oxadiazolyl, triazolyl, pyridyl, bipyridyl, pyrimidyl, triazine, acridinyl, pyrazolyl, pyrazinyl, quinolyl, quinazolinyl, quinoxalinyl, phthalazinyl, pyridopyrimidyl, pyridopyrazinyl, pyrazinopyrazinyl, isoquinolyl, indolyl, carbazolyl, benzoxazolyl, benzimidazolyl, benzothiazolyl, benzocarbazolyl, benzothienyl, dibenzothienyl, benzofuranyl, phenanthroline, isoxazolyl, thiadiazolyl, phenothiazinyl, dibenzofuranyl, etc., but the present invention is not limited thereto.
[0230] In addition, the Group 4 transition metal may be titanium (Ti), zirconium (Zr), hafnium (Hf) or (Rf), and specifically titanium (Ti), zirconium (Zr), and hafnium (Hf). More specifically, it may be zirconium (Zr) or hafnium (Hf), but is not limited thereto.
[0231] In addition, the Group 13 element may be boron (B), aluminum (Al), gallium (Ga), indium (In), or thallium (Tl), and specifically boron (B) or aluminum (Al), but is not limited thereto.
[0232] The above-mentioned substituents may be optionally substituted with one or more substituents selected from the group consisting of a hydroxyl group; a halogen group; an alkyl group or an alkenyl group, an aryl group, an alkoxy group; an alkyl group or an alkenyl group, an aryl group, an alkoxy group containing at least one hetero atom among hetero atoms of Groups 14 to 16; a silyl group; an alkylsilyl group or an alkoxysilyl group; a phosphine group; a phosphide group; a sulfonate group; and a sulfone group, within the range of exhibiting the same or similar effects as the desired effects.
[0233] Furthermore, “two adjacent substituents are bonded to each other to form an aliphatic ring or an aromatic ring” means that atoms of the two substituents and atoms bonding to the two substituents are bonded to each other to form a ring.
[0234] Specifically, -NR9R 10 R9 and R 10 Examples of groups connected to each other to form an aliphatic ring include piperidinyl, -NR9R 10 R9 and R 10 Examples of groups linked to each other to form an aromatic ring include pyrrolyl.
[0235] In the catalyst composition, the first metallocene compound represented by Chemical Formula 6 is a ligand Cp 1 and Cp 2 The invention also reduces the non-crosslinked compounds and favors the production of mainly low molecular weight copolymers with low SCB (short chain branch) content.
[0236] Specifically, in Chemical Formula 6, the ligand Cp 1 and Cp 2 may be the same as or different from each other, and may each be a cyclopentadienyl group and substituted with one or more or one to three C 1-10 Alkyl. Since the ligand Cp 1 and Cp 2 It has a pair of non-covalent electrons that can act as a Lewis base, so it can achieve high polymerization activity. In particular, since the ligand Cp 1 and Cp 2They are cyclopentadienyl groups with relatively low steric hindrance, so they exhibit high polymerization activity and low hydrogen reactivity, and thus can polymerize low molecular weight polyethylene with high activity.
[0237] In addition, the ligand Cp 1 and Cp 2 The properties of the polyethylene to be prepared, such as chemical structure, molecular weight, molecular weight distribution, mechanical properties and transparency, can be easily controlled by adjusting the degree of steric hindrance according to the type of substituted functional group. 1 and Cp 2 R a and R b Replacement, where R a and R b are the same as or different from each other and may each independently be hydrogen, C 1-20 Alkyl, C 2-20 Alkoxyalkyl, C 7-40 Arylalkyl, or a substituted or unsubstituted C containing at least one heteroatom selected from the group consisting of N, O and S 2-12 Heteroaryl, and more specifically C 1-10 Alkyl, C 2-10 Alkoxyalkyl, C 7-20 Arylalkyl, or a substituted or unsubstituted C containing at least one heteroatom selected from the group consisting of N, O and S 4-12 Heteroaryl.
[0238] In addition, M 2 Z 2 3-m Present in ligand Cp 1 and Cp 2 Between, and M 2 Z 2 3-m Can affect the storage stability of the metal complex. In order to effectively ensure this effect, Z 1 can be independently halogen or C 1-20 Alkyl, more specifically F, Cl, Br or I. In addition, M 2 Each independently may be Ti, Zr or Hf; Zr or Hf; or Zr.
[0239] The first metallocene compound may be a compound wherein Cp 1 and Cp 2 are each an unsubstituted or substituted cyclopentadienyl group, and R a and R b are independently hydrogen, C 1-10 Alkyl, C 2-10 Alkoxyalkyl or C 7-20Arylalkyl, wherein R a and R b At least one of them is an alkoxyalkyl group, such as tert-butoxyhexyl, more specifically a substituent -(CH2) p -OR c (Among them, R c is a linear or branched alkyl group having 1 to 6 carbon atoms, and p is an integer of 2 to 4). In addition, compared with other Cp-based catalysts not containing the above-mentioned substituents, this case shows a low conversion rate of the comonomer when polyethylene is prepared using the comonomer, so that a low molecular weight polyethylene with a controlled degree of copolymerization or comonomer distribution can be prepared. In addition, when the first metallocene compound having the above-mentioned structure is supported on a carrier, the -(CH2) in the substituent is p -OR c The groups can form covalent bonds through close interaction with silanol groups on the surface of silica used as a support, thereby enabling stable supported polymerization.
[0240] The first metallocene compound represented by Chemical Formula 6 may be a compound represented by one of the following structural formulas, but is not limited thereto:
[0241]
[0242] The first metallocene compound represented by Chemical Formula 6 may be synthesized by applying a known reaction, and a more specific synthesis method may be understood with reference to the Examples.
[0243] Meanwhile, in one embodiment of the present invention, the second metallocene compound represented by Chemical Formula 7 comprises an aromatic ring compound containing a cyclopentadienyl group or a derivative thereof and a nitrogen atom, and has the aromatic ring compound and the nitrogen atom connected by a bridging group T 2 Q 3 Q 4 The second metallocene compound having such a specific structure is suitable for the polymerization reaction of ethylene / 1-hexene copolymer to show high activity and copolymerizability, and can provide a high molecular weight olefin copolymer.
[0244] In particular, the second metallocene compound represented by Chemical Formula 7 has a well-known CGC (constrained geometry catalyst) structure, so the introduction of comonomers is excellent, and the distribution of comonomers is controlled by the electronic and spatial properties of the ligands. These properties control ASL (average ethylene sequence length) to increase the medium and high molecular weight regions in the molecular weight distribution, thereby increasing the tied molecule fraction and the entanglement of the polymer chain. Therefore, it is easy to prepare a polyethylene resin that exhibits long-term stability and processability and has excellent mechanical properties.
[0245] M of the metallocene compound represented by Chemical Formula 73 It may be a Group 4 transition metal, and may preferably be titanium (Ti), zirconium (Zr), or hafnium (Hf).
[0246] Preferably, T in Chemical Formula 7 2 It may be silicon.
[0247] Preferably, X in Chemical Formula 7 3 and X 4 Each may independently be methyl or chlorine (Cl).
[0248] Preferably, R in Chemical Formula 7 11 To R 14 The same as or different from each other, and may each independently be a methyl group or a phenyl group.
[0249] Preferably, two or more adjacent R 11 To R 14 are connected to each other to form a substituted or unsubstituted aliphatic ring, a substituted or unsubstituted aromatic ring, or a substituted or unsubstituted heteroaromatic ring containing at least one selected from the group consisting of N, O and S. For example, in Chemical Formula 7, since two or more R adjacent to each other 11 To R 14 The indenyl, fluorenyl, benzothienyl and dibenzothienyl groups are connected to form an aliphatic ring, an aromatic ring or a heteroaromatic ring, so that an indenyl, fluorenyl, benzothienyl or dibenzothienyl group fused with cyclopentadiene can be formed. In addition, the indenyl, fluorenyl, benzothienyl and dibenzothienyl groups can be substituted by more than one substituent.
[0250] Preferably, R in Chemical Formula 7 15 To R 16 The groups may be the same as or different from each other, and may each independently be a methyl group, an ethyl group, a phenyl group, a propyl group, a hexyl group, or a tert-butoxyhexyl group.
[0251] Preferably, R in Chemical Formula 7 17 It may be methyl, ethyl, n-propyl, isopropyl, n-butyl or tert-butyl.
[0252] Since the second metallocene compound can provide a polyethylene resin that is excellent in long-term stability and processability and has excellent mechanical properties due to an increase in the medium and high molecular weight region, the metallocene compound of Chemical Formula 7 may be any one selected from the group consisting of the following compounds, but the present invention is not limited thereto:
[0253]
[0254] The second metallocene compound represented by Chemical Formula 7 can be synthesized by applying known reactions. Specifically, it can be prepared by connecting a nitrogen compound to a cyclopentadiene derivative with a bridging compound to prepare a ligand compound, and then adding a metal precursor compound to perform metalation. However, the method is not limited thereto, and a more specific synthesis method can be understood with reference to the embodiments and synthesis examples.
[0255] The second metallocene compound represented by Chemical Formula 7 has excellent activity and can polymerize a high molecular weight polyethylene resin. In particular, even when supported on a carrier for use, it exhibits high polymerization activity, and thus can prepare an ultra-high molecular weight polyethylene resin.
[0256] In addition, even when the polymerization reaction is carried out in the presence of hydrogen to prepare a polyethylene resin with a high molecular weight and a wide molecular weight distribution, the second metallocene compound represented by Chemical Formula 7 of the present invention exhibits low hydrogen reactivity, and thus an ultrahigh molecular weight polyethylene resin can be copolymerized with high activity. Therefore, even when used in combination with a catalyst having other characteristics, a polyethylene resin satisfying high molecular weight characteristics can be prepared without deteriorating activity, and thus a polyethylene resin having a wide molecular weight distribution while containing a high molecular weight polyethylene resin can be easily prepared.
[0257] As described above, in the catalyst composition, the first metallocene compound represented by Chemical Formula 6 can mainly promote the production of a low molecular weight copolymer having a low SCB content, and the second metallocene compound represented by Chemical Formula 7 can mainly promote the production of a high molecular weight copolymer having a high SCB content. More specifically, the catalyst composition exhibits a high comonomer incorporation amount to the comonomer in the high molecular weight region of the copolymer through the second metallocene compound, and the catalyst composition exhibits a low comonomer incorporation amount to the comonomer in the low molecular weight region of the copolymer through the first metallocene compound. As a result, a polyethylene resin exhibiting excellent heat resistance by having a bimodal molecular weight distribution and having excellent mechanical properties can be prepared.
[0258] In particular, controlling the content ratio of the first and second metallocene compounds in the catalyst composition can achieve the above-mentioned physical properties and further enhance the improvement effect. Specifically, when the content of the second metallocene compound in the catalyst composition is higher than that of the first metallocene compound, the medium and high molecular weight regions in the molecule increase so that the entanglement of the tethered molecule fraction and the polymer chain increases, thereby optimizing the ratio of the high molecular weight region to the low molecular weight region.
[0259] Specifically, the molar ratio of the first and second metallocene compounds contained should be 1:2 to 1:8. Preferably, the molar ratio of the first and second metallocene compounds contained may be 1:3 to 1:7, 1:4 to 1:6 or 1:4.5 to 1:5.5. When the first and second metallocene compounds are contained within the above range, the polyethylene resin thus prepared controls the balance between mechanical properties and elongation. Therefore, it maintains mechanical properties, productivity and tensile stability equivalent to or superior to conventional materials, and can improve high shrinkage resistance, printability and transparency.
[0260] Meanwhile, the first and second metallocene compounds have the above-mentioned structural features, so they can be stably supported on the carrier.
[0261] In this case, the first and second metallocene compounds are used in a state supported on a carrier. When used as a supported catalyst, the polymer to be prepared has excellent particle shape and bulk density, and the catalyst can be appropriately used for conventional slurry polymerization, bulk polymerization and gas phase polymerization.
[0262] The support may be silica, alumina, magnesia or silica-magnesia, and may generally contain oxides, carbonates, sulfates or nitrates, such as Na2O, K2CO3, BaSO4, Mg(NO3)2, etc. Among the above supports, the silica support hardly releases the catalyst from the surface during the polymerization process because the transition metal compound is supported by chemical bonding with reactive functional groups such as siloxane groups present on the surface of the silica support. As a result, when a polymer is prepared by slurry polymerization or gas phase polymerization, the fouling phenomenon (adherence to the reactor wall surface or to each other) can be minimized.
[0263] In addition, in order to increase the loading efficiency and minimize leaching and scaling, the support can be surface modified by calcination or drying. Through the surface modification step as described above, the moisture on the support surface that inhibits the reaction with the supported component can be removed, and the content of reactive functional groups (such as hydroxyl groups and siloxane groups) that can chemically bond with the supported component can be increased.
[0264] Specifically, the calcination or drying process of the carrier can be carried out in a temperature range from the temperature at which moisture disappears from the surface of the carrier to the temperature at which reactive functional groups (especially hydroxyl groups (OH groups) present on the surface) are completely eliminated. Specifically, the temperature can be 150 to 600°C or 200 to 500°C. When the temperature is relatively low, below 150°C, the water removal efficiency is low, and as a result, the moisture remaining on the carrier can react with the co-catalyst to reduce the loading efficiency. When the temperature is too high, above 600°C, the pores on the surface of the carrier can be combined with each other to reduce the specific surface area, and a large amount of reactive functional groups such as hydroxyl groups or silanol groups may be lost on the surface, leaving only siloxane groups. Therefore, the reaction sites with the co-catalyst may be reduced, which is not preferred.
[0265] When the first and second metallocene compounds are supported on a carrier and the carrier is silica, the total supported amount of the first and second metallocene compounds may be 40 μmol or more or 80 μmol or more, and may be 240 μmol or less or 160 μmol or less based on 1 g of silica. When supported within the above range, suitable supported activity may be exhibited, which is advantageous in terms of maintaining catalyst activity and economic feasibility.
[0266] Furthermore, the catalyst composition may further contain a co-catalyst in terms of improving high activity and process stability.
[0267] In the hybrid supported metallocene catalyst of the present invention, the type and content of the co-catalyst further included are as described above, and the detailed description is omitted.
[0268] For example, among the above compounds, the cocatalyst may be more specifically an alkylaluminoxane-based cocatalyst such as methylaluminoxane.
[0269] In addition, the alkylaluminoxane-based cocatalyst stabilizes the metallocene compound and acts as a Lewis acid, thereby further enhancing the catalytic activity by including a metal element capable of forming a bond with the functional group of the bridging group introduced into the second metallocene compound through Lewis acid-base interaction.
[0270] In addition, the cocatalyst used can be appropriately adjusted according to the desired properties or effects of the catalyst and the resin composition. For example, when silica is used as a carrier, the loading amount of the cocatalyst can be 8 mmol or more or 10 mmol or more based on the weight of the carrier (e.g., 1 g of silica), and can be 25 mmol or less or 20 mmol or less.
[0271] In addition, the above-mentioned catalyst composition can be used for polymerization as it is, or can be used in a prepolymerized state by contacting with a polypropylene monomer before being used in a polymerization reaction. In this case, the preparation method of one embodiment of the present invention can also include a prepolymerization step of contacting the catalyst composition with an ethylene monomer before preparing polyethylene by a polymerization reaction.
[0272] In addition, the catalyst composition may be dissolved or diluted in the following materials and then injected: an aliphatic hydrocarbon solvent having 5 to 12 carbon atoms such as pentane, hexane, heptane, nonane, decane and isomers thereof, an aromatic hydrocarbon solvent such as toluene and benzene, or a hydrocarbon solvent substituted with chlorine such as dichloromethane and chlorobenzene. The solvent used herein is preferably used after being treated with a small amount of alkylaluminum to remove a small amount of water or air as a catalyst poison. A cocatalyst may further be used.
[0273] Meanwhile, the polymerization process may be performed by contacting ethylene with a comonomer in the presence of the above-mentioned catalyst composition. In particular, the polymerization reaction may be performed in a bi-mode form using two or more reactors, or in a single polymerization reactor.
[0274] The polymerization may be performed at a temperature of 25° C. to 500° C., preferably 25° C. to 200° C., and more preferably 50° C. to 150° C. In addition, the polymerization may be performed at 1 kgf / cm 2 Up to 100kgf / cm 2 , preferably 1kgf / cm 2 Up to 50kgf / cm 2 And more preferably 5kgf / cm 2 Up to 30kgf / cm 2 under pressure.
[0275] In addition, in the copolymerization process, the input amount of 1-hexene as a comonomer may be about 4.0 wt% to about 6.0 wt% based on the total input weight of ethylene. More specifically, the input amount of 1-hexene may be about 4.1 wt% or more, about 4.2 wt% or more, about 4.3 wt% or more, about 4.4 wt% or more, or about 4.5 wt% or more, and may be about 5.9 wt% or less, about 5.8 wt% or less, 5.6 wt% or less, about 5.4 wt% or less, about 5.2 wt% or less, or about 5.0 wt% or less.
[0276] Meanwhile, the polyethylene resin of the present invention may be prepared by copolymerizing ethylene and a comonomer in the presence of the above-mentioned catalyst composition while introducing hydrogen.
[0277] For example, the amount of hydrogen introduced may be 35 ppm to 250 ppm, 40 ppm to 200 ppm, 50 ppm to 190 ppm, 55 ppm to 180 ppm, 58 ppm to 170 ppm, or 60 ppm to 145 ppm based on the weight of ethylene.
[0278] In the step of supporting the catalyst precursor on the support supported by the co-catalyst, the supported catalyst may be prepared by adding the first and second transition metal compounds to the support supported by the co-catalyst, stirring, and then further adding the co-catalyst.
[0279] In the mixed supported metallocene catalyst of the present invention, the amounts of the support, the co-catalyst, the support supported with the co-catalyst and the transition metal compound can be appropriately adjusted according to the desired properties or effects of the supported catalyst.
[0280] Meanwhile, when the molar ratio of the first transition metal compound to the second transition metal compound (first transition metal compound: second transition metal compound) is less than 1:0.3, it is difficult to produce ultra-low density polyethylene due to the reduced amount of comonomer introduced. When the ratio exceeds 1:5.5, it is difficult to reproduce the molecular structure of the desired polymer.
[0281] At this time, the loading amount of the metallocene compound supported on the silica carrier may be 0.01 to 1 mmol / g based on 1 g of the carrier. That is, considering the promoting effect of the metallocene compound on the catalyst, it is preferred to control the loading amount within the above range.
[0282] When a mixed supported catalyst is prepared, the reaction solvent may be a hydrocarbon solvent such as pentane, hexane and heptane; or an aromatic hydrocarbon solvent such as benzene and toluene.
[0283] For the details of the preparation method of the supported catalyst, refer to the embodiment to be described later. However, the preparation method of the supported catalyst is not limited to this specification. The preparation method can also include the steps commonly performed in the technical field of the present invention, and the steps of the preparation method can be changed by commonly changeable steps.
[0284] Meanwhile, the above-mentioned polyethylene copolymer may be prepared by a method including the step of copolymerizing ethylene and α-olefin in the presence of the above-mentioned mixed supported metallocene catalyst.
[0285] The hybrid supported catalyst can exhibit excellent supporting performance, catalytic activity and high comonomer incorporation amount, and can prepare a polyethylene copolymer capable of producing a biaxially stretched film having excellent ductile processing area and mechanical properties.
[0286] The preparation of the second ethylene-α-olefin copolymer (b) can be carried out by a slurry polymerization process using ethylene and α-olefin as raw materials in the presence of the above-mentioned mixed supported catalyst with conventional equipment and contact technology.
[0287] The second ethylene-α-olefin copolymer (b) may be prepared by copolymerizing ethylene and α-olefin using a continuous slurry polymerization reactor, a ring slurry reactor, etc., but the present invention is not limited thereto.
[0288] That is, in the case of the mixed supported metallocene catalyst of the present invention in which the first metallocene compound and the second metallocene compound are supported within the above molar ratio, the processability and shrinkage and mechanical properties of the polyethylene copolymer can be further improved due to the interaction of two or more catalysts.
[0289] In the mixed supported metallocene catalyst of the present invention, the support for supporting the first metallocene compound and the second metallocene compound, the further included cocatalyst and the polymerization process are the same as those described above for the first ethylene-α-olefin copolymer (a), and the specific details are omitted.
[0290] The second ethylene-α-olefin copolymer (b) of the present invention can be prepared by copolymerizing ethylene and α-olefin using the above-mentioned supported metallocene catalyst.
[0291] By the above-mentioned preparation method, the second ethylene-α-olefin copolymer (b) having the above-mentioned physical properties can be prepared.
[0292] Biaxially stretched film
[0293] The polyethylene composition having the above-mentioned physical properties can stably form a biaxially stretched film having high shrinkage resistance, printability and transparency while maintaining excellent mechanical properties, productivity and stretching stability.
[0294] Meanwhile, the biaxially stretched film may be produced by a conventional film production method except that the above-mentioned polyethylene composition is used.
[0295] For example, in order to produce the polyethylene biaxially stretched film of the present invention, a polyethylene composition sheet having a thickness of 0.75 mm can be prepared using a laboratory extruder line manufactured by Bruckner (L / D ratio: 42, pitch: 25 mm, melt / T die temperature: 220°C). Thereafter, a polyethylene biaxially stretched film can be prepared by biaxially stretching a polyethylene composition sheet having a length and width of 90 mm×90 mm using a KARO 5.0 device. The specific method and conditions are as described in Test Example 3 described below.
[0296] In addition, the polyethylene biaxially stretched film of the present invention may also contain additives well known in the art in addition to the above-mentioned polyethylene copolymer. Specifically, such additives may include solvents, heat stabilizers, antioxidants, ultraviolet absorbers, light stabilizers, metal deactivators, fillers, reinforcing agents, plasticizers, lubricants, emulsifiers, pigments, optical brighteners, flame retardants, antistatic agents, foaming agents, etc. The type of additive is not particularly limited, and conventional additives known in the art may be used.
[0297] The polyethylene biaxially stretched film according to one embodiment of the present invention prepared by the above method may have improved performance and have excellent extensible processing area characteristics and mechanical properties.
[0298] In particular, the polyethylene biaxially oriented film may be stretched with an MD stretching ratio of 4 times or more or 5 times or more, and a TD stretching ratio of 6 times or more or 8 times or more.
[0299] The polyethylene biaxially stretched film may have a tensile strength of 80 MPa or more, or 80 MPa to 150 MPa, in the MD direction (MD / machine direction, film length direction, longitudinal direction) measured according to ASTM D 882. The polyethylene biaxially stretched film may have a tensile strength of 110 MPa or more, or 110 MPa to 250 MPa, in the TD direction (TD / transverse direction, film width direction, transverse direction) measured according to ASTM D 882.
[0300] In addition, the polyethylene biaxially stretched film may have a tensile modulus in the MD direction of 700 MPa or more, or 700 MPa to 1500 MPa, and a tensile modulus in the TD direction of 800 MPa or more, or 800 MPa to 1600 MPa, measured according to ASTM D 882.
[0301] The polyethylene biaxially stretched film may have a tensile elongation in the MD direction measured according to ASTM D 882 of 200% to 300%, or 220% to 280%, and a tensile elongation in the TD direction of 70% to 140%, or 85% to 125%.
[0302] The polyethylene biaxially stretched film may have a tear strength in the MD direction measured according to ASTM 1992 of 6 N / mm to 14.8 N / mm, and a tensile strength in the TD direction of 2.5 N / mm to 6.8 N / mm.
[0303] In addition, the polyethylene biaxially stretched film may have a haze of 3% or less, or 3% or less and 0% or more, as measured according to ASTM 1003. Preferably, the polyethylene biaxially stretched film may have a haze of 2.8% or less, or 2.5% or less, or 2.3% or less, 2.2% or less, 2.0% or less, or 1.9% or less. Considering the practical limitations of the physical properties of the film, the haze may be 0.1% or more, 0.5% or more, 1.0% or more, 1.5% or more, or 1.6% or more.
[0304] The 45° glossiness of the biaxially stretched polyethylene film measured according to ASTM 2457 may be 80 GU or more, or 80 GU to 100 GU, preferably 85 GU or more, 88 GU or more, 90 GU or more, or 94 GU or more.
[0305] In addition, the polyethylene biaxially stretched film has excellent stretchability and stretching stability, so it can be stretched as follows: the MD stretch ratio is greater than 4 times, or 5 times or more, and the TD stretch ratio is greater than 6 times, or 7 times or more. For example, while satisfying the condition that the biaxially stretched film is stretched with an MD stretch ratio of 4 times or more and a TD stretch ratio of 6 times or more, the total shrinkage rate of the polyethylene biaxially stretched film in the MD / TD direction measured after shrinking at 100° C. for 7 minutes according to ASTM D1204 (i.e., the sum of the MD shrinkage rate and the TD shrinkage rate of the polyethylene biaxially stretched film) can be 6.0% or less, or 5.9% or less, or 5.8% or less; or the total shrinkage rate in the MD / TD direction (i.e., the sum of the MD shrinkage rate and the TD shrinkage rate of the polyethylene biaxially stretched film) measured after shrinking at 120° C. for 7 minutes according to ASTM D 1204 is 22.0% or less, or 21.5% or less, or 21% or less.
[0306] The tensile strength of the polyethylene biaxially stretched film in the MD direction measured according to ASTM D 882 may be 100 MPa or more, 110 MPa or more, or 120 MPa or more, and may be 150 MPa or less, and the tensile strength in the TD direction may be 180 MPa or more, 190 MPa or more, or 200 MPa or more, and may be 250 MPa or less.
[0307] Therefore, the average MD tensile strength and TD tensile strength of the biaxially stretched film measured according to ASTM D 882 may be 130 MPa or more, preferably 140 MPa or more, 150 MPa or more, or 160 MPa or more, and may be 200 MPa or less.
[0308] Furthermore, the tensile modulus of the polyethylene biaxially stretched film in the MD direction may be 600 MPa or more, or 645 MPa or more and 1000 MPa or less, and the tensile modulus in the TD direction may be 800 MPa or more, or 900 MPa or more and 1500 MPa or less.
[0309] Therefore, the average MD tensile modulus and TD tensile modulus of the biaxially stretched film measured according to ASTM D 882 may be 700 MPa or more, preferably 750 MPa or more, 780 MPa or more, or 794.5 MPa or more, and may be 1000 MPa or less.
[0310] The polyethylene biaxially stretched film may have a tensile elongation in the MD direction measured according to ASTM D 882 of 150 to 250% or 160 to 230%, and a tensile elongation in the TD direction of 50 to 100% or 65 to 90%.
[0311] The polyethylene biaxially stretched film may have a tear strength in the MD direction measured according to ASTM 1992 of 6 N / mm to 13.1 N / mm, and a tear strength in the TD direction of 1.6 N / mm to 6.7 N / mm.
[0312] In addition, the puncture strength of the polyethylene biaxially stretched film measured according to EN 14477 may be 300 N / mm or more. Preferably, the puncture strength may be 320 N / mm or more, 340 N / mm or more, or 357 N / mm or more, and may be 400 N / mm or less.
[0313] In the present invention, the physical properties of the biaxially stretched film may be measured according to the above standards, and the specific methods are as described in Test Example 3 which will be described hereinafter.
[0314] In the present invention, the first ethylene-α-olefin copolymer having excellent fluidity to impart stretchability is blended with the first ethylene-α-olefin copolymer having excellent mechanical properties to adjust the balance between mechanical properties and elongation. Therefore, a biaxially stretched film having high shrinkage resistance, printability and transparency can be stably manufactured while maintaining excellent mechanical properties, productivity and tensile stability.
[0315] Beneficial Effects
[0316] The polyethylene of the present invention has an excellent effect of producing a biaxially stretched film having high shrinkage resistance, printability and transparency while maintaining excellent mechanical properties, productivity and stretching stability. DETAILED DESCRIPTION
[0317] Hereinafter, embodiments of the present invention will be described in more detail in the following examples. However, the following examples are for illustrative purposes only and are not intended to limit the present invention.
[0318] Example
[0319] <Preparation of Metallocene Compound>
[0320] Synthesis example 1
[0321]
[0322] (1) Preparation of ligand compounds
[0323] Synthesis of N-tert-butyl-1-(1,2-dimethyl-3H-benzo[b]cyclopenta[d]thiophen-3-yl)-1,1-dimethylsilylamine
[0324] 4.65 g (15.88 mmol) of the compound of Chemical Formula 1 was added to a 100 mL Schlenk flask, and then 80 mL of THF was added thereto. After tBuNH2 (4 equivalents, 6.68 mL) was added at room temperature, the mixture was reacted at room temperature for 3 days. After the reaction, THF was removed and the mixture was filtered with hexane. After the solvent was dried, 4.50 g (yield: 86%) of a yellow liquid was obtained.
[0325] 1 H-NMR (500MHz, CDCl3): δ7.99 (d, 1H), 7.83 (d, 1H), 7.35 (dd, 1H), 7.24 (dd, 1H), 3.49(s, 1H), 2.37(s, 3H), 2.17(s, 3H), 1.27(s, 9H), 0.19(s, 3H), -0.17(s, 3H).
[0326] (2) Preparation of transition metal compounds
[0327] The ligand compound (1.06g, 3.22mmol / 1.0 equivalent) and MTBE 16.0mL (0.2M) are added to a 50mL schlenk flask and stirred first. At -40 ° C, n-BuLi (2.64mL, 6.60mmol / 2.05 equivalent, 2.5M THF solution) is added and reacted overnight at room temperature. Thereafter, MeMgBr (2.68mL, 8.05mmol / 2.5 equivalent, 3.0M ether solution) is slowly added dropwise at -40 ° C, and TiCl4 (2.68mL, 3.22mmol / 1.0 equivalent, 1.0M toluene solution) is then added thereto at room temperature, and then reacted overnight. Hexane is then used to filter through diatomaceous earth. After the solvent is dried, 1.07g (yield: 82%) of a brown solid is obtained.
[0328] 1 H-NMR (500MHz, CDCl3): δ7.99 (d, 1H), 7.68 (d, 1H), 7.40 (dd, 1H), 7.30 (dd, 1H), 3.22 (s, 1H), 2.67 (s, 3H), 2.05 (s, 3H), 1.54 (s, 9H), 0.58 (s, 3H), 0.57 (s, 3H), 0.40 (s, 3H), -0.45 (s, 3H).
[0329] Synthesis example 2
[0330]
[0331] t-Bu-O-(CH2)6-Cl was prepared by the method shown in Tetrahedron Lett. 2951 (1988) using 6-chlorohexanol, and reacted with Na(C5H5)[NaCp] to give t-Bu-O-(CH2)6-C5H5 (yield 60%, boiling point 80°C / 0.1 mmHg).
[0332] In addition, t-Bu-O-(CH2)6-C5H5 is dissolved in tetrahydrofuran (THF) at -78°C, and n-BuLi is slowly added thereto. Thereafter, it is heated to room temperature and reacted for 8 hours. The lithium salt solution synthesized as above is slowly added to a suspension solution (170g, 4.50mmol) / THF (30mL) of ZrCl4(THF)2 at -78°C, and further reacted at room temperature for about 6 hours. All volatiles are vacuum dried and the resulting oily liquid material is filtered by adding hexane solvent. The filtered solution is vacuum dried, and hexane is added at low temperature (-20°C) to obtain a precipitate. The resulting precipitate is filtered at low temperature to obtain [t-Bu-O-(CH2)6-C5H4]2ZrCl2 compound (yield 92%) in the form of a white solid.
[0333] 1 H-NMR (300MHz, CDCl3): δ6.28 (t, J=2.6Hz, 2H), 6.19 (t, J=2.6Hz, 2H), 3.31 (t, 6.6Hz, 2H), 2.62 (t, J=8Hz), 1.7-1.3 (m, 8H), 1.17 (s, 9H).
[0334] 13 C-NMR (CDCl3): δ135.09, 116.66, 112.28, 72.42, 61.52, 30.66, 30.31, 30.14, 29.18, 27.58, 26.00.
[0335] Synthesis example 3
[0336]
[0337] 50 g of Mg (solid) was added to a 10 L reactor at room temperature, followed by 300 mL of THF. 0.5 g of I2 was added and the reactor temperature was maintained at 50°C. After the reactor temperature stabilized, 250 g of 6-tert-butoxyhexyl chloride was added to the reactor at a flow rate of 5 mL / min using a feed pump. It was observed that the reactor temperature rose by 4 to 5°C with the addition of 6-tert-butoxyhexyl chloride. Stir for 12 hours while continuously adding 6-tert-butoxyhexyl chloride. After reacting for 12 hours, a black reaction solution was obtained. 2 mL of the black solution was taken and water was added thereto to obtain an organic layer. By 1 H-NMR confirmed that the organic layer was 6-tert-butoxyhexane. This confirmed that the Grignard reaction had sufficiently proceeded. Thus, 6-tert-butoxyhexylmagnesium chloride was synthesized.
[0338] 500g of MeSiCl3 and 1L of THF were added to the reactor, and then the reactor temperature was cooled to -20°C. 560g of the 6-tert-butoxyhexylmagnesium chloride synthesized above was added to the reactor at a flow rate of 5mL / min using a feed pump. After the supply of the Grignard reagent was completed, the mixture was stirred for 12 hours while the reactor temperature was slowly raised to room temperature. After 12 hours of reaction, the production of MgCl2 salt was confirmed. 4L of hexane was added thereto and the salt was removed by labdori to obtain a filtered solution. After the filtered solution was added to the reactor, the hexane was removed at 70°C to obtain a light yellow liquid. By 1 H-NMR confirmed that the obtained liquid was methyl(6-tert-butoxyhexyl)dichlorosilane.
[0339] 1 H-NMR (300MHz, CDCl3): δ3.3 (t, 2H), 1.5 (m, 3H), 1.3 (m, 5H), 1.2 (s, 9H), 1.1 (m, 2H), 0.7 (s, 3H).
[0340] 1.2 mol (150 g) of tetramethylcyclopentadiene and 2.4 L of THF were added to the reactor, and then the reactor temperature was cooled to -20 ° C. 480 mL of n-BuLi was added to the reactor at a flow rate of 5 mL / min using a feed pump. After adding n-BuLi, the mixture was stirred for 12 hours while the reactor temperature was slowly raised to room temperature. After 12 hours of reaction, 1 equivalent of methyl (6-tert-butoxyhexyl) dichlorosilane (326 g, 350 mL) was quickly added to the reactor. The mixture was stirred for 12 hours while the reactor temperature was slowly raised to room temperature. Then, the reactor temperature was cooled to 0 ° C again, and 2 equivalents of t-BuNH2 were added. The mixture was stirred for 12 hours while the reactor temperature was slowly raised to room temperature. After 12 hours of reaction, THF was removed. Thereafter, 4 L of hexane was added to remove salts through a labdori to obtain a filtered solution. The filtered solution was added to the reactor again, and the hexane was removed at 70 ° C to obtain a yellow solution. By 1 H-NMR confirmed that the yellow solution obtained above was methyl(6-tert-butoxyhexyl)(tetramethyl CpH)tert-butylaminosilane.
[0341] TiCl3(THF)3 (10 mmol) was quickly added to the dilithium salt of the ligand synthesized from n-BuLi and dimethyl(tetramethylCpH)tert-butylaminosilane ligand synthesized in THF solution at -78°C. The reaction solution was stirred for 12 hours while slowly heating from -78°C to room temperature. After stirring for 12 hours, 1 equivalent of PbCl2 (10 mmol) was added to the reaction solution at room temperature, which was then stirred for 12 hours. After stirring for 12 hours, a dark black solution with a slight bluish tint was obtained. THF was removed from the resulting reaction solution, and hexane was then added to filter the product. Hexane was removed from the filtered solution, and then filtered by 1 H-NMR confirmed that the product was (tBu-O-(CH2)6)(CH3)Si(C5(CH3)4)(tBu-N)TiCl2([methyl(6-tert-butoxyhexyl)silyl(η5-tetramethylCp)(tert-butylamido)]TiCl2).
[0342] 1 H-NMR (300MHz, CDCl3): δ3.3 (s, 4H), 2.2 (s, 6H), 2.1 (s, 6H), 1.8-0.8 (m), 1.4 (s, 9H), 1.2 (s, 9H), 0.7 (s, 3H).
[0343] <Preparation of supported catalyst>
[0344] Catalyst Preparation Example 1: Preparation of Mixed Supported Metallocene Catalyst
[0345] 5.0 kg of the toluene solution was added to a 20 L stainless steel (sus) high pressure reactor, and the reactor temperature was maintained at 40° C. 1000 g of silica (manufactured by GraceDavison, SYLOPOL 948) dehydrated by applying vacuum at a temperature of 600° C. for 12 hours was added to the reactor and fully dispersed, and then 80 g of the first metallocene compound of Synthesis Example 2 was dissolved in the toluene solution and added thereto, followed by stirring at 200 rpm for 2 hours at 40° C. to react. Thereafter, stirring was stopped, standing was performed for 30 minutes, and the reaction solution was decanted.
[0346] 2.5 kg of toluene was added to the reactor, and 9.4 kg of 10 wt% methylaluminoxane (MAO) / toluene solution was added thereto, followed by stirring at 200 rpm for 12 hours at 40°C. After the reaction, the mixture was allowed to stand for 30 minutes, and the reaction solution was decanted. After 3.0 kg of toluene was added and stirred for 10 minutes, stirring was stopped, the mixture was allowed to stand for 30 minutes, and the toluene solution was decanted.
[0347] 3.0 kg of toluene was added to the reactor, and then 314 mL of a 29.2 wt % second metallocene compound of Synthesis Example 3 / toluene solution was added to the reactor, followed by stirring at 200 rpm for 2 hours at 40° C. to react. At this time, the molar ratio of the first metallocene compound to the second metallocene compound was 1:5. After the reactor temperature was lowered to room temperature, stirring was stopped, the mixture was allowed to stand for 30 minutes, and the reaction solution was decanted.
[0348] After adding 2.0 kg of toluene and stirring for 10 minutes, stirring was stopped, and the mixture was allowed to stand for 30 minutes, and the reaction solution was decanted.
[0349] 3.0 kg of hexane was added to the reactor, and the hexane slurry was transferred to a filter dryer and the hexane solution was filtered and dried under reduced pressure at 40° C. for 4 hours to prepare 910 g of a SiO2 mixed supported catalyst.
[0350] <Preparation of ethylene-α-olefin copolymer>
[0351] Preparation Example 1: Preparation of ethylene / 1-octene copolymer (PE-a)
[0352] While adding 5 kg / h of hexane solvent and 0.31 kg / h of 1-octene, a 1.5 L continuous process reactor was preheated at 120° C. Triisobutylaluminum (Tibal, 0.045 mmol / min), the transition metal compound obtained in Synthesis Example 1, and dimethylanilinium tetrakis(pentafluorophenyl)borate cocatalyst (2.6 μmol / min) were added to the reactor simultaneously. Subsequently, in a continuous process at a pressure of 89 bar, ethylene (0.87 kg / h) and hydrogen (10 cc / min) were introduced into the reactor and maintained at 160.0° C. for more than 60 minutes to carry out copolymerization to obtain an ethylene / 1-octene copolymer (PE-a).
[0353] Preparation Example 2: Preparation of ethylene / 1-hexene copolymer (PE-b)
[0354] In the presence of the supported mixed catalyst prepared in Catalyst Preparation Example 1, an ethylene / 1-hexene copolymer (PE-b) was subjected to slurry polymerization.
[0355] At this time, the polymerization reactor is an isobutane (i-C4) slurry loop process, a continuous polymerization reactor, and the reactor volume is 140L, and the flow rate is about 7m / second. The gases (ethylene, hydrogen) and comonomer 1-hexene required for polymerization are constantly and continuously introduced, and the flow rate is adjusted according to the target product. At this time, the ethylene input is 31.1kg / hour, the 1-hexene input is adjusted to 2.5% by weight compared with ethylene, and the hydrogen input is adjusted to 56ppm compared with ethylene. In addition, the concentrations of all gases and 1-hexene comonomers in Preparation Example 1 were confirmed by an online gas chromatograph. A supported catalyst was prepared and introduced as an isobutane slurry with a concentration of 4% by weight, the reactor pressure was maintained at about 40bar, and the polymerization temperature was about 80°C.
[0356] <Test Example 1: Evaluation of Physical Properties of Polyethylene>
[0357] The physical properties of the ethylene-α-olefin copolymers prepared in Preparation Examples 1 to 2 were measured by the following methods and are shown in Table 1.
[0358] (1) Melt index
[0359] Melt index (MI) was measured at 190°C under a load of 2.16 kg according to ASTM D 1238 (Condition E, 190°C, 2.16 kg) of the American Society for Testing and Materials. 2.16 ) (measuring apparatus: MI-4 manufactured by Gottfert) and expressed as the weight (g) of the polymer melted within 10 minutes.
[0360] (2) Density
[0361] Density (g / cm2) was measured using a density gradient column according to ASTM D 1505 (American Society for Testing and Materials). 3 ).
[0362] (3) Number average molecular weight, weight average molecular weight and molecular weight distribution
[0363] Regarding the ethylene-α-olefin copolymers prepared in Preparation Examples 1 to 2, the molecular weight distribution (Mw / Mn, PDI, polydispersity index) was calculated by measuring the weight average molecular weight (Mw, g / mol) and the number average molecular weight (Mn, g / mol) using gel permeation chromatography (GPC, manufactured by Water) according to ASTM D 6474 (American Society for Testing and Materials), and then dividing the weight average molecular weight by the number average molecular weight.
[0364] Specifically, PL-GPC220 manufactured by Water was used as a gel permeation chromatography (GPC) instrument, and a Polymer Laboratories PLgel MIX-B 300mm long column was used. The evaluation temperature was 160°C, and 1,2,4-trichlorobenzene was used as a solvent at a flow rate of 1 mL / min. Each ethylene-alpha olefin copolymer prepared in Preparation Examples 1 to 2 was dissolved in 1,2,4-trichlorobenzene containing 0.0125% of BHT at 160°C for 10 hours for pretreatment, and a sample with a concentration of 10 mg / 10 mL was supplied in an amount of 200 μL. The calibration curve formed using a polystyrene standard sample was used to obtain Mw and Mn values. Nine polystyrene standards were used with molecular weights of 2000 g / mol, 10000 g / mol, 30000 g / mol, 70000 g / mol, 200000 g / mol, 700000 g / mol, 2000000 g / mol, 4000000 g / mol and 10000000 g / mol.
[0365] [Table 1]
[0366]
[0367] Comparative Preparation Example 1
[0368] The ethylene / 1-butene copolymer produced by Ziegler-Natta catalyst, namely the commercial product ME1000 TM (manufactured by LG Chem Co., Ltd.) was used as Comparative Example 1 (PE-c).
[0369] Comparative Preparation Example 2
[0370] The ethylene homopolymer produced by metallocene catalyst, namely the commercially available SP380 TM(manufactured by LG Chem Co., Ltd.) was used as Comparative Example 2 (PE-d).
[0371] <Preparation of Polyethylene Composition>
[0372] Examples 1 to 3 and Comparative Examples 1 to 3
[0373] The polyethylene compositions of Examples 1 to 3 and Comparative Examples 1 to 3 were prepared with the compositions shown in Table 2 below using the above-mentioned ethylene-α-olefin copolymers or ethylene homopolymers (homo PE) of Preparation Examples 1 to 2 and Comparative Preparation Examples 1 to 2, respectively.
[0374] Specifically, the polyethylene composition was prepared by extrusion and pelletization at 220° C. using a twin extruder (extruder: TEK30MHS from SMPLATEK, L / D ratio: 40, die diameter: 4 mm) with a hopper at 18 rpm and a screw at 350 rpm.
[0375] <Test Example 2: Evaluation of physical properties of polyethylene composition>
[0376] Physical properties of the polyethylene compositions prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were measured by the following methods and are shown in Table 2.
[0377] First, the melt index (MI) of the polyethylene composition was measured in the same manner as in Test 1 above. 2.16 ), density, weight average molecular weight (Mw, g / mol), number average molecular weight (Mn, g / mol) and molecular weight distribution (Mw / Mn, PDI).
[0378] (4) Melting temperature, crystallization temperature and crystallinity
[0379] The melting temperature (Tm), crystallization temperature (Tc), and crystallinity (Xc) of the polyethylene compositions of Examples 1 to 3 and Comparative Examples 1 to 3 were measured using a differential scanning calorimeter (DSC, equipment name: DSC Q20, manufacturer: TA instrument).
[0380] Specifically, the polyethylene composition is heated to 180°C at 10°C / min (cycle 1), isothermally maintained at 180°C for 5 minutes, cooled to 0°C at 10°C / min, isothermally maintained at 30°C for 5 minutes, and then heated to 180°C at 10°C / min again (cycle 2). In the DSC curve obtained above, the temperature at the maximum point of the endothermic peak is measured as the melting point (Tm, °C), and the temperature at the maximum point of the exothermic peak is measured as the crystallization temperature (Tc, °C). At this time, the melting point (Tm) and the crystallization temperature (Tc) are shown as the measurement results in the second cycle 2 of heating and cooling.
[0381] In addition, the heat of fusion ΔHm was obtained by calculating the area of the melting peak in the second cycle of heating and cooling 2, and the crystallinity (Xc) was calculated by dividing ΔHm by H 0 m=293.6 J / g (theoretical value when the crystallinity is 100%).
[0382] (5) Cross-fractionation chromatography (CFC)
[0383] The polyethylene compositions of Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to cross fractionation chromatography (CFC) in the following manner. The main chain weight average molecular weight (Mw main,T≥90℃ ), the content ratio of the high crystalline fraction eluted above 90°C (TREF T≥90℃ ) and the content ratio of the medium and low crystalline fraction eluted at less than 90°C (TREF T<90℃ ).
[0384] Cross Fractionation Chromatography (CFC) Measurement Conditions (including TREF and GPC-IR analysis)
[0385] -Analysis equipment: Polymer Char CFC (Detector: Integrated detector IR5MCT)
[0386] -Sample preparation and injection: 32 mg of the polyethylene composition was added to a 10 mL vial and placed in an autosampler. Then, 8 mL of 1,2,4-trichlorobenzene (TCB) was added, dissolved at 160°C for 90 minutes, extracted after nitrogen purge, and then injected into a temperature rising elution fractionation column (TREF column).
[0387] - Crystallization: After the temperature of the sample previously injected into the TREF column was adjusted to 100°C, cooling from 100°C to 35°C was performed at 0.5°C / min.
[0388] - Temperature Rising Elution Fractionation (TREF) analysis: A previously crystallized sample is heated from 35°C to 120°C at intervals of 1°C and fixed. Then, the fractions eluted at each temperature within 25 minutes are analyzed. Specifically, it is possible to extract and analyze at 35°C for 25 minutes, then extract and analyze after increasing the temperature at intervals of 1°C, and finally extract and analyze at 120°C for 25 minutes.
[0389] -GPC-IR analysis: The fractions eluted at each temperature in the previous TREF analysis were transferred to the GPC column of the GPC (PL-GPC220) apparatus, the molecular weights of the eluted molecules were measured, and the number of short chain branches (scb) of the molecules eluted at each temperature was measured using a PerkinElmer Spectrum 100 FT-IR connected to the GPC (PL-GPC220).
[0390] -Main chain weight average molecular weight (Mw main,T≥90℃ ): The weight average molecular weight (Mw) of the main chain (excluding short chain branches) of the high crystalline fraction eluted at 90°C or above of the polyethylene composition as confirmed by CFC analysis of the polyethylene composition. main,T≥90℃ ) is calculated by the following equation 1.
[0391] [Equation 1]
[0392]
[0393] In Equation 1, M T,i and C T,i are the weight average molecular weight (g / mol) and concentration of each fraction eluted at each measurement temperature, respectively, obtained by the above-mentioned CFC analysis of the polyethylene composition.
[0394] n scb T,i is the number of short chain branches (scb) of each fraction eluted at each measurement temperature, respectively, obtained by the above CFC analysis of the polyethylene composition, and
[0395] M scb is the weight average molecular weight (g / mol) of the short chain branch (scb) of each fraction eluted at each measurement temperature, respectively, obtained by the above-mentioned CFC analysis of the polyethylene composition.
[0396] - High crystalline fraction content ratio: The content ratio of the high crystalline fraction eluted at 90° C. or higher (TREF) is calculated as a percentage (%) based on the total weight of all eluted fractions of the polyethylene composition obtained by the above CFC analysis. T≥90℃ ).
[0397] - Content ratio of medium and low crystalline fraction: The content ratio of the medium and low crystalline fraction eluted at less than 90° C. (TREF T<90℃ ).
[0398] (6) Relaxation time
[0399] The relaxation times of the polyethylene compositions of Examples 1 to 3 and Comparative Examples 1 to 3 were measured.
[0400] Specifically, the relaxation time (seconds) of the polyethylene composition is obtained by measuring the viscosity at each temperature of 150°C, 170°C, 190°C, 210°C and 230°C and an angular frequency of 0.05 rad / second to 500 rad / second using a rotational rheometer ARES-G2 manufactured by TA Instruments (New Castle, Delaway, USA) under a stress of 0.5% and a frequency of 0.1 rad / second to 500 rad / second, and then calculating the relaxation time (seconds) using the crossover model of the following equation 2 using the viscosity.
[0401] [Equation 2]
[0402] η=η ∞ +(η0-η ∞ ) / (1+λ×(shear rate) m )
[0403] In equation 2,
[0404] η is the viscosity of the polyethylene composition measured using a rotational rheometer at each of 150° C., 170° C., 190° C., 210° C. and 230° C. and an angular frequency of 0.05 rad / sec to 500 rad / sec,
[0405] η ∞ is the infinite shear viscosity,
[0406] η0 is the zero shear viscosity,
[0407] Shear rate is the shear rate applied to the polyethylene composition and is equal to the angular frequency,
[0408] λ and m are parameters that fit a log-log plot with angular frequency on the x-axis and viscosity η on the y-axis to the crossover model of Equation 2,
[0409] λ is the relaxation time (seconds) of the polyethylene composition and is the inverse of the angular frequency at which the viscosity η starts to decrease, and
[0410] m is the slope of the viscosity η in the region where the viscosity η decreases.
[0411] In addition, as described above, the 120° C. relaxation time (seconds) was calculated at 120° C. from the Arrhenius curve based on the values of the relaxation time (seconds) at each temperature.
[0412] For example, the Arrhenius constant (A) is obtained by an Arrhenius curve according to the value of the relaxation time (second) at each temperature, and then the relaxation time of the polyethylene composition is calculated according to the following Equation 3.
[0413] [Equation 3]
[0414] lnK=LnA+E a / RT
[0415] In equation 3,
[0416] K is the relaxation time of the polyethylene composition (seconds),
[0417] E a is the activation energy (J / mol),
[0418] R is the gas constant (8.314 J / mol·K),
[0419] A is the Arrhenius constant, and
[0420] T is the absolute temperature (Kelvin).
[0421] [Table 2]
[0422]
[0423] <Test Example 3: Preparation of biaxially stretched film and evaluation of physical properties>
[0424] Biaxially stretched films were prepared by the following method using the polyethylene compositions prepared in Examples 1 to 3 and Comparative Examples 1 to 3, and then physical properties thereof were measured and shown in Table 3.
[0425] Preparation of biaxially stretched films
[0426] - A polyethylene composition sheet having a thickness of 0.75 mm was prepared using a laboratory extruder line manufactured by Bruckner (L / D ratio: 42, pitch: 25 mm, melt / T die temperature: 220°C)
[0427] - Biaxial stretching of a polyethylene composite sheet with a length and width of 90 mm x 90 mm using a KARO 5.0 machine
[0428] -After preheating for 80 seconds under the following conditions, stretching (MD→TD) was performed in sequence: Example 1: preheating and stretching at 120°C, Example 2: preheating and stretching at 125°C, Example 3: preheating and stretching at 122°C, Comparative Example 1: preheating and stretching at 115°C, Comparative Example 2: preheating and stretching at 125°C, Comparative Example 3: Stretching was attempted under the same conditions as in Example 2, but it was confirmed that stretching could not be performed.
[0429] Evaluation of physical properties of biaxially stretched films
[0430] - Tensile strength (MPa), tensile modulus (MPa) and tensile elongation (%): measured in MD / TD directions according to ASTM D 882 standard.
[0431] - Tear strength (N / mm): measured in MD / TD direction according to ASTM 1922 standard.
[0432] -Haze (%): measured according to ASTM 1003 standard.
[0433] -45° Gloss: Measured according to ASTM 2457.
[0434] - Shrinkage (%): The length change was measured after shrinking at 100° C. or 120° C. for 7 minutes according to ASTM D 1204. Specifically, the shrinkage (%) was measured as [(1−length after shrinkage) / length before shrinkage]×100.
[0435] -Puncture strength (N / mm): According to EN 14477 standard.
[0436] [Table 3]
[0437]
[0438] According to the results of Tables 2 and 3, it is confirmed that the composition of the embodiment that meets the predetermined main chain weight average molecular weight has excellent stretchability and tensile stability compared with the comparative example, and has outstanding tensile stability and high shrinkage resistance when manufactured as a biaxially stretched film, and exhibits excellent mechanical properties.
Claims
1. A polyethylene composition comprising at least one ethylene-alpha olefin copolymer, in, The main chain weight average molecular weight (Mw) of the highly crystalline fraction eluting above 90°C from the cross fractionation chromatography (CFC) analysis of the polyethylene composition main,T≥90℃ ) is less than 150000 g / mol.
2. The polyethylene composition according to claim 1, in, The polyethylene composition comprises (a) Density: 0.870 g / cm 3 Up to 0.920g / cm 3 And the melt index (MI 2.16 , 190° C., 2.16 kg load) of 3.0 g / 10 minutes to 10.0 g / 10 minutes of a first ethylene-alpha olefin copolymer; and (b) Density: 0.930 g / cm 3 Up to 0.960g / cm 3 And the melt index (MI 2.16 , 190°C, 2.16 kg load) in a range of 0.2 g / 10 min to 2.0 g / 10 min of a second ethylene-alpha olefin copolymer.
3. The polyethylene composition according to claim 1, in, The main chain weight average molecular weight (Mw) of the highly crystalline fraction eluting above 90°C from the cross fractionation chromatography (CFC) analysis of the polyethylene composition main,T≥90℃ ) is 50000 g / mol to 150000 g / mol.
4. The polyethylene composition according to claim 1, in, The content ratio of the high crystalline fraction eluting above 90°C (TREF) from the cross fractionation chromatography (CFC) analysis of the polyethylene composition T≥90℃ ) is more than 50% of the total weight of all eluted fractions.
5. The polyethylene composition according to claim 1, in, The content ratio of the medium and low crystalline fraction eluting at less than 90°C (TREF) from the cross fractionation chromatography (CFC) analysis of the polyethylene composition T<90℃ ) is less than 50% of the total weight of all eluted fractions.
6. The polyethylene composition according to claim 1, in, The relaxation time (RT) of the polyethylene composition at 120°C 120℃ ) is less than 4.0 seconds.
7. The polyethylene composition according to claim 1, in, The density of the polyethylene composition is 0.928 g / cm 3 Up to 0.942g / cm 3 Below, and melt index (MI 2.16 , 190°C, 2.16kg load) is 0.6g / 10min to 1.5g / 10min.
8. The polyethylene composition according to claim 1, in, The polyethylene composition has a number average molecular weight (Mn) of 25,000 g / mol or more, a weight average molecular weight (Mw) of 105,000 g / mol or more, and a molecular weight distribution (Mw / Mn) of 5.0 or less.
9. The polyethylene composition according to claim 1, in, The polyethylene composition has a melting point (Tm) of 125° C. to 129° C., a crystallization temperature (Tc) of 112° C. to 115° C., and a crystallinity (Xc) of 35% to 48%.
10. The polyethylene composition according to claim 2, in, The polyethylene composition comprises a first ethylene-α-olefin copolymer (a) in an amount greater than 0 wt% and 40 wt% or less and a second ethylene-α-olefin copolymer (b) in an amount greater than 60 wt% and less than 100 wt%.
11. The polyethylene composition according to claim 2, in, The first ethylene-α-olefin copolymer (a) has a number average molecular weight (Mn) of 20,000 g / mol or more, a weight average molecular weight (Mw) of 60,000 or more and 95,000 g / mol or less, and a molecular weight distribution (Mw / Mn) of 2.0 or more and less than 3.
5.
12. The polyethylene composition according to claim 2, in, The first ethylene-α-olefin copolymer (a) comprises at least one α-olefin selected from the group consisting of 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene and 1-eicosene.
13. The polyethylene composition according to claim 2, in, The first ethylene-α-olefin copolymer (a) is an ethylene / 1-octene copolymer.
14. The polyethylene composition according to claim 2, in, The second ethylene-α-olefin copolymer (b) has a number average molecular weight (Mn) of 20,000 g / mol or more, a weight average molecular weight (Mw) of 95,000 or more and 150,000 g / mol or less, and a molecular weight distribution (Mw / Mn) of 3.5 or more and 4.8 or less.
15. The polyethylene composition according to claim 2, in, The second ethylene-α-olefin copolymer (b) comprises at least one α-olefin selected from the group consisting of 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene and 1-eicosene.
16. The polyethylene composition according to claim 2, in, The second ethylene-α-olefin copolymer (b) is an ethylene / 1-hexene copolymer. 17 . A biaxially stretched film comprising the polyethylene composition according to claim 1 .
18. The biaxially stretched film according to claim 17, in, The biaxially stretched film is stretched at an MD stretching ratio of 4 times or more and a TD stretching ratio of 6 times or more.
19. The biaxially stretched film according to claim 17, in, While satisfying the conditions that the biaxially stretched film is stretched at an MD stretching ratio of 4 times or more and a TD stretching ratio of 6 times or more, The sum of the MD shrinkage and the TD shrinkage of the biaxially stretched film measured after shrinkage at 100°C for 7 minutes according to ASTM D 1204 is 6.0% or less, or The sum of the MD shrinkage and the TD shrinkage of the biaxially stretched film measured after shrinkage at 120° C. for 7 minutes according to ASTM D 1204 is 22.0% or less.
Citation Information
Patent Citations
Patch for extending storage of vegetable and fruits and thereof method
KR1020220120055A
Atomic layer deposition apparatus and atomic layer deposition method using the same
KR1020230126269A